Hurricane wind field representation shapes storm surge and building-scale flood hazard estimates - Mithun Deb; Robert D. Hetland; Michael F. Wehner; Zhaoqing Yang; Karthik Balaguru; Ning Sun; Ali Abdolali (Coastal Engineering, 2026)

Differences in the regulation of soil carbon quality and stability by topsoil and deep soil under grazing - Jiali Sun; Shichao Tian; Haihua Bai; Ahmed F. El‑Shafie; Mohamed E. Abuarab; Ali Mokhtar; Zifeng Zhao; Xiaomeng Guo; Wei Qin; Fei Li (Agriculture, Ecosystems & Environment, 2026)

Development and mechanical evaluation of stress-line inspired ribbed timber slabs with stay-in-place formwork - Hua Chai; Yiting Sun; Zhan Shu; Haipeng Hu; Philip F. Yuan (Engineering Structures, 2026)

What have we learned about Australia’s swampy meadows? a literature review - Alex Sun; Floris F. van Ogtrop (Wetlands Ecology and Management, 2026)
Scientists coined the term ‘swampy meadows’ over thirty years ago to describe a type of low-energy, discontinuous watercourse found in the valley fills of Southeastern Australia. Swampy meadows are believed to provide important ecosystem services, such as wildlife conservation and water security; but to assess these claims, scientists must first understand the hydrology, geomorphic history, cultural value, and ecological significance of swampy meadows. In this paper, we reviewed literature from The Web of Science, Scopus, and Google Scholar to find that most published articles on swampy meadows are geomorphological studies of degraded systems. While these studies are important and must continue, we argue that they alone are insufficient to resolve the longstanding debates surrounding swampy meadow conservation and restoration. To make further progress on these debates, scientists should compare swampy meadows across multiple catchments, especially those that are still considered ‘intact’, and expand the scope of their current research to include topics such as biology and socio-economy. Scientists should also address directly the questions and claims raised in grey literature on the costs and benefits of restoring swampy meadows. We argue that the most effective way to protect swampy meadows is to first identify the cultural values and ecosystem services they provide, then establish management policies around these values and services.

Serpentinization in Jezero crater: Comparing SuperCam Mars data to terrestrial serpentinites - J.M. Comellas; S.K. Sharma; P.J. Gasda; A. Cousin; A. Essunfeld; P. Fryer; L.E. Mayhew; L. Sun; A.J. Brown; T.E. Acosta-Maeda; E. Dehouck; M. Veneranda; et al. (Icarus, 2026)

Association of exposure to phthalates and substitutes with infection risk among U.S. children - Yu Zhang; Siqi Jin; Zichuan Li; Liang Wang; Mariana F. Fernández; Ainhoa Pérez-Cantero; Yang Sun; Yi-Xin Wang; Carmen Messerlian; Vicente Mustieles (Environmental Pollution, 2026)

Settling by water: Human habitation adapted to landscape evolution at the Xuecheng site in the lower reaches of the Yangtze River during the Mid-late Holocene - Zhiping Zhang; Zhujun Hu; Xingyu Zhou; Hui Peng; Jue Sun; Jiahao Xu; Hongwei Shi; Lin Yang; Ping Zhang; Feng Xu; Harry F. Lee; Xin Jia (Science China Earth Sciences, 2026)

The role of tropical inter-basin interactions in initiating the 2020–2023 La Niña: a hindcast-based predictability study - Nahid A. Hasan; Yoshimitsu Chikamoto; Wei Zhang; Michael J. McPhaden; Malte F. Stuecker; June-Yi Lee; Yong-Yub Kim; Sun-Seon Lee (Climate Dynamics, 2026)
The recent triple-dip La Niña event from 2020 to 2023 in the equatorial Pacific, which occurred without a preceding strong El Niño, challenges the traditional understanding of multi-year La Niña dynamics governed solely by the recharge oscillator theory. This study investigates the mechanisms behind the initiation of the 2020–2023 La Niña and evaluates the predictive capabilities of a fully coupled climate model. Utilizing a multi-year climate prediction system based on the Community Earth System Model version 2 with ocean data assimilation techniques, we assess the contributions of various climate factors, including inter-basin forcings such as the Indian Ocean Dipole (IOD) and tropical Atlantic warming (TAW). Our findings reveal that, while the model underestimates the role of the IOD, the combination of positive IOD and TAW substantially influenced first-dip La Niña initiation through the eastward propagation of velocity potential anomalies. Partial ocean data assimilation experiments corroborate these results and further suggest that accurately predicting the phases of the Pacific Meridional Mode (PMM) is essential for forecasting the initiation process. Our hindcast experiment indicates that the La Niña event typically decays within one year rather than persisting, suggesting that distinct drivers, such as PMM, South Pacific, or aerosol forcing, may have influenced the second and third phases of cooling. These insights highlight the critical role of inter-basin interactions (IOD, TAW, and PMM forcings) in extending ENSO predictability and improving long-term climate forecasting capabilities.

Reciprocal adaptation is critical in enhancing S. aureus and P. aeruginosa biofilm biomass - Xiaohan Sun; Clare M. Cooksley; Muhammed Awad; Emma F. Barry; Alkis J. Psaltis; Peter-John Wormald; Sarah Vreugde (Archives of Microbiology, 2026)
Polymicrobial communities impose a great challenge for clinical management of chronic infections. It is a consensus now that microbes exist as aggregated colonies shielded within polymeric matrix. Within this matrix more than one bacterial species can exist either in symbiotic or rival relationships. Herein, we investigated the host-specific interspecies interactions between Staphylococcus aureus and Pseudomonas aeruginosa in chronic rhinosinusitis (CRS). The indirect interaction between the two species was assessed using Transwell co-culture chambers, where S. aureus and P. aeruginosa ( n = 3 each) derived from CRS patients were cultured in separate chambers that allowed exchange of soluble factors. Later the biofilm biomass of each species was evaluated and compared to single species biofilm. Further, the influence of the co-culture conditions on antibiotic tolerance was evaluated. When derived from the same patient, co-cultured bacteria increased the biofilm biomass of each other significantly by 3.0-4.9 fold ( p p

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Correction to “Choline chloride enables low-severity NaOH/Triton-X 100 pretreatment and lignin upgrading to enriched aromatic bio-oil and porous biochar” [Chem. Eng. J. 2026;538:176853. https://doi.org/10.1016/j.cej.2026.176853] - S. Al Azad; E. Kargaran; M. Saleknezhad; Y. Cheng; C. Quan; J. Chen; C. Sun; M. Madadi; F. Sun (Chemical Engineering Journal, 2026)

Multi-decadal resilience (2002–2023) of subtropical coral communities in the Solitary Islands, eastern Australia, despite severe cumulative disturbances - Hamish A. Malcolm; Marine Lechene; Renata Ferrari; Curtis Champion; Steven J. Dalton; Maria Beger; James Cant; Fiona Chong; Wanchien Victoria Hsiao; Sun W. Kim; Liam Lachs; Stephen D. A. Smith; et al. (Coral Reefs, 2026)

National Evidence of Depth‐Dependent Stabilization and Controls of Soil Organic Carbon in Dryland Croplands - Yuchen Wei; Xin Zhao; Wenting Feng; Hongyong Sun; Jinfeng Chang; Hong Chen; Ji Chen; Xiaowei Guo; Di He; Feng Liu; Alain F. Plante; Zhou Shi; et al. (Global Change Biology, 2026)
Soil organic carbon (SOC) underpins agricultural sustainability and the terrestrial carbon cycle, yet its vertical distribution and stabilization across soil depth remain poorly constrained at large spatial scales. Here, we present a nationwide, depth‐resolved dataset of SOC and mineral‐associated organic carbon (MAOC)—the more persistent SOC fraction—from 365 dryland cropland sites across China, sampled to 2 m depth. Contrary to the classic model of exponential SOC decline, 46% of profiles exhibited uniform or increasing SOC and MAOC with depth, highlighting a substantial role of subsoil carbon. MAOC accounted for more than half of total SOC in most layers, but its relative contribution declined below 1 m, challenging the assumption that subsoil carbon is inherently more stable. Clay + silt content was the strongest predictor for SOC, MAOC, and MAOC/SOC across depths, while vegetation productivity, a proxy for carbon inputs, was positively associated with all three. The influence of clay + silt on MAOC accumulation weakened with depth, and the positive interaction between vegetation productivity and clay + silt weakened or diminished from surface soils to deeper layers. These patterns indicate a transition from joint regulation by carbon inputs and mineral surfaces in surface soils toward an increasingly input‐limited regime in deeper layers, as inferred from the depth‐dependent changes in the relative importance of vegetation productivity and fine particle content. National mapping estimated ~19.9 Pg SOC stored within the 0–2 m layer in China's dryland croplands, with 75% below 0.3 m and 60% stabilized as MAOC. These results provide a benchmark for depth‐explicit SOC accounting and highlight the importance of aligning carbon inputs with soil mineralogy to enhance whole‐profile carbon stabilization and climate mitigation.

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Regional immunity in the respiratory tract: challenges and opportunities - Shuo Wang; Si Chen; Lianpan Dai; Fengqi Li; Hui Li; Kefang Liu; Xiangzhi Meng; Jian Wang; Hua Yue; Airu Zhu; Bin Cao; Ling Chen; et al. (Science Bulletin, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Heavy metals and per- and polyfluoroalkyl substances in breast milk: associations with infant birth outcomes in an E-waste recycling area - Yueyuan Fan; Hui Wang; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Cheng‑Sheng Zhu; Xian Liang Sun (Environmental Geochemistry and Health, 2026)

NAD+ depletion transdifferentiates the gastric stem cells to intestinal goblet cells in patient-derived gastric organoids - Bin Liu; Xiaoyang Zhang; Xia Xue; Fazhan Li; Feifei Ren; Ihtisham Bukhari; Baitong Hu; Xiangdong Sun; Bo Zhang; Yong Yu; Quan Zheng; Wanqing Wu; et al. (Chemical Engineering Journal, 2026)

Mechanistic investigation of nitrogen-doped carbon nanotubes for enhancing periodate reactions - X. Wang; T. Sun; A. Obaid; L. Gao; Y. Wang; F. Zhang; D. Hao (International Journal of Environmental Science and Technology, 2026)
In recent years, carbon catalysts have emerged as an efficient choice for green treatment of organic wastewater. Despite extensive research on carbonaceous materials in advanced oxidation processes, challenges such as low activation efficiency and limited reusability hinder their large-scale application. Therefore, a deeper understanding of the catalytic mechanisms of non-metallic carbon materials in advanced oxidation processes is crucial for optimizing their performance. In this study, nitrogen-doped carbon nanotubes are investigated as effective activators of periodate for the degradation of sulfisoxazole which is a sulfonamide antibiotic and a potential carcinogenic frequently detected in wastewater. Experimental results of this study demonstrated that under optimized conditions nitrogen-doped carbon nanotubes/periodate system attained 100% sulfisoxazole elimination efficiency within 20 min, with the apparent degradation rate increasing by up to 3.5 times as the nitrogen doping level increased. Comprehensive mechanistic studies involving quenching experiments, chemical probe analysis and electron paramagnetic resonance revealed two fundamental degradation pathways: 1) a radical pathway in which the graphitic nitrogen sites on nitrogen-doped carbon nanotubes significantly activated periodate to produce hydroxyl radicals and 2) a non-radical pathway, facilitated by structural defects of nitrogen-doped carbon nanotubes that mediate direct electron transfer between sulfisoxazole and periodate and continue to oxidize sulfisoxazole. This study highlights the potential of N-doped carbon nanotubes to enhance periodate-based oxidation and furnishes critical insights for the rational design of carbon-based catalysts in environmental remediation applications. Graphical abstract

Hums in the humus: opportunities and challenges for soil ecoacoustics - Alex F. Taylor; Martin F. Breed; Carlos Abrahams; Amy Annells; Tom Bradfer-Lawrence; Timothy Cavagnaro; Carolyn-Monika Görres; Martin M. Gossner; Craig Liddicoat; Simon Linke; Oliver C. Metcalf; Louise Roberts; et al. (Trends in Ecology & Evolution, 2026)

2,3,3,3-Tetrafluoropropene (1234yf) polymerization and inhibition - Sheng Peng; Anthony F. Stasio; Jian Sun-Blanks; Mary E. Koban (Journal of Fluorine Chemistry, 2026)

A stimuli-responsive polymeric ferroptosis drug delivery system for treatment of liver metastases - Deqiang Deng; Muyang Yang; Zhen Zeng; Tianbing Xu; Yuanyuan Geng; Weicheng Tang; Yao Sun; Jonathan F. Lovell; Lisen Lu; Mingxin Zhu; Honglin Jin (Chemical Engineering Journal, 2026)

Enzymatic production of prebiotic xylooligosaccharides - Lucas F. Almeida; Lanyu Li; Ronald P. de Vries; Peicheng Sun; Gabriela Piccolo Maitan-Alfenas (World Journal of Microbiology and Biotechnology, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

A comprehensive investigation of the diet and subsistence strategies of the Bronze Age population in the Northern Agro-pastoral ecotone of China - Xin Jia; Wei Wang; Hongwei Shi; Chuang Wang; Xujia Pan; Runqi Jiang; Yonggang Sun; Harry F. Lee; Yaowu Hu (Quaternary Science Reviews, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Synergistic potential of clove oil and Bacillus culture filtrates (CFs) in suppressing the natural infection of Fusarium wilt pathogen in tomato - Muhammad Imran; Munirah F. Aldayel; Maryam M. Alomran; Reham A. Abd El Rahman; Kamal A. M. Abo-Elyousr; Muhammad Saqib Bilal; Zhongke Sun (Plant and Soil, 2026)

Ocean dynamics in 2025: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Diego Bruciaferri; Sandro Carniel; Amin Chabchoub; W. Bryce Corlett; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Tsubasa Kodaira; et al. (Ocean Dynamics, 2026)

Harnessing virtual screening and MD simulations: a multistage approach to identifying potent and nontoxic agonists for protein kinase A - Muneeb Ali; Nadeem Ahmad; Madiha Sardar; Sajjad Haider; Mamona Mushtaq; Mohammad Nur-e-Alam; Mohammed F. Hawwal; Pinghua Sun; Zaheer Ul-Haq (Molecular Diversity, 2026)

Research on pollution in highway pavement construction: an approach based on improved AHP and grey clustering method - J. Sun; W. Ling; S. Yang; F. Xiang (International Journal of Environmental Science and Technology, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

Revealing Structural Brain-Cognition Relationships in Children: A Comparison of Morphometric Similarity and INverse Divergence Networks - Shuning Han; Hao Jia; Gemma Vilaseca; Núria Vilaró; Feng Duan; Zhe Sun; Cesar F. Caiafa; Jordi Solé-Casals (Neuroinformatics, 2026)
The study of structural brain networks (SBNs) offers critical insights into brain-cognition relationships. However, a comprehensive comparison of these methods in terms of their topological properties, cognitive relevance, and sensitivity to connection density remains lacking. This study compares two types of individual-level SBNs–morphometric similarity networks (MSNs) and morphometric inverse divergence (MIND) networks–by analyzing their associations with cognitive performance using sMRI data from 29 male children. Group- and individual-level analyses were conducted to evaluate differences in hemispheric connectivity, topological features, and their correlations with cognitive performance across different connection densities. In our analyses, a connection density of $$p=0.05\sim 0.15$$ appeared optimal for stabilizing network properties and maximizing cognitive correlations in both MSN and MIND. Moreover, advanced network segregation and integration metrics (such as local efficiency and node versatility, along with their global summaries) demonstrated greater sensitivity to cognitive performance. However, MSNs appeared to provide a more reliable framework, demonstrating more stable associations across connection densities in topological and hemispheric dimensions. Specifically, higher cognitive performance may be linked to stronger left intra-hemispheric connectivity, weaker inter-hemispheric connectivity, and more modular network organization–consistent with established theories of hemispheric specialization and efficient modularity. In contrast, MIND networks exhibit reduced effectiveness and stability across metrics and densities in our data. These preliminary insights enhance our understanding of brain-cognition relationships and provide practical guidelines for parameter selection and metric identification in network-based cognitive analyses.

Inter-comparison of soybean models for simulation of evapotranspiration under rainfed and irrigated conditions - Kritika Kothari; Andrew Suyker; Rafael Battisti; Kenneth J. Boote; Sotirios Archontoulis; Julie Constantin; Santiago V. Cuadra; Philippe Debaeke; Elvis F. Elli; Babacar Faye; David Fleisher; Brian Grant; et al. (Agricultural and Forest Meteorology, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Urban organic manure application enhances antibiotic resistance gene diversity and potential human pathogen abundance in invasive giant African snails - Zhonghui Tang; Yiyue Zhang; Huayuan Shangguan; An Xie; Xueli Xu; Yong Jiang; Martin F. Breed; Xin Sun (Journal of Environmental Sciences, 2025)

The role of submarine volcanism in atmospheric chemistry - M. Colombier; M. Bonifacie; M. Brenna; A. Burke; C. Cimarelli; S.J. Cronin; P. Delmelle; D.B. Dingwell; K-U. Hess; M. Huebsch; T. Kula; F. Latu’ila; et al. (Earth and Planetary Science Letters, 2025)

Vortex-induced vibrations of variable cross-section CWPs under axially varying tension: Numerical investigation with three flow profiles - Jian Tan; Yu Zhang; Yulong Zhang; Le Sun; Shuai Cui; Chen An; Segen F. Estefen (Ocean Engineering, 2025)

Source-specific insights into photochemical and microbial degradation of dissolved organic matter in coastal environments - Bin Wang; Xuelu Gao; Simon F. Thrush; Yongliang Liu; Xiyan Sun; Jianmin Zhao; Qianguo Xing; Yuwei Yang (Marine Environmental Research, 2025)

Can useful biomarker information be obtained from museum fossil specimens treated with Paraloid® B-72 acrylic resin? - Luke M. Brosnan; Stephen F. Poropat; Madison Tripp; Sebastian Stanley; Peter Hopper; Xiao Sun; William D.A. Rickard; Antônio Á.F. Saraiva; Renan A.M. Bantim; Juliana M. Sayão; Alexander W.A. Kellner; Kliti Grice (Organic Geochemistry, 2025)

Biocontrol of postharvest soft rot caused by Rhizopus stolonifer in sweet potatoes using volatile organic compounds from actinomycete Nocardiopsis dassonvillei MI-S24 - Abd El-Rahman F Gomaa; Jing Tao; Sun-Yan Liang; Jia-Qi Liu; Si Yang; Xiao-Qiong Shi; Mohamed H. El-Sayed; Ke Xing; Sheng Qin (Food Control, 2025)

P18-20 Building Bridges in Tobacco Harm Reduction: A Global Interlaboratory Initiative for Standardized Smoke and Aerosol Exposure Assessment - M. Caruso; R. Emma; P. Zuccarello; S. Rust; G. Carota; K. Poulas; F. Zadjali; A. Sun; V. Volarevic; R. Lesmana; M. Tobi; K. Mesiakaris; et al. (Toxicology Letters, 2025)

Children’s home environments as reservoirs of antimicrobial resistance: Divergent urban-rural risks from antibiotic resistance genes and pathogens - Shuang Du; Hao Tang; Zhang Wang; Han Chen; Xinyi Fang; Jin Sun; Zhiping Niu; Yiwei Liu; Yuanzhuo Hu; Wen Su; Zhenhua Zhang; Tippawan Prapamontol; et al. (Journal of Hazardous Materials, 2025)

Fast hydrothermal and microwave synthesis of high purity methylated imogolite nanotubes - Y. Zhang; F. Alfadel Raad; P. Picot; F. Gobeaux; A. Thill; X. Sun; D. Schaming; L. Sicard (Applied Clay Science, 2025)

The future of urban cycling: A predictive framework for climate change - Xudong Wang; Eduardo Adame Valenzuela; Chenglong You; Van-Thanh-Van Nguyen; Lijun Sun; Luis F. Miranda-Moreno (Transportation Research Part D: Transport and Environment, 2025)

Unraveling the origin and charge of Halahatang oils, Tarim Basin - Peng Sun; Chunfang Cai; Daowei Wang; Yu Qi; Chenlu Xu; Paul F. Greenwood (Organic Geochemistry, 2025)

Comparing inward and outward strategies for delimiting non-native plant pest outbreaks - Hongyu Sun; Jacob C. Douma; Martijn F. Schenk; Wopke van der Werf (Journal of Pest Science, 2025)

Impact of dispersion correction in DFT-enhanced anisotropic NMR for stereochemical elucidation of flexible marine natural products - Lu-Ping Chi; Xiao-Lu Li; Anton F. Ketzel; Armando Navarro-Vázquez; Caspar J. Schattenberg; Xiao-Ming Li; Xin Li; Han Sun; Bin-Gui Wang (Marine Life Science & Technology, 2025)
Although anisotropic NMR spectroscopy has emerged as a powerful method for determining the relative configuration of complex natural products, major challenges persist with structurally flexible molecules. In this study, we conducted a systematic comparative analysis of stereochemical elucidation, combining anisotropic NMR spectroscopy and density functional theory (DFT) calculations on spiroepicoccin B ( 1 ) and epicoccin V ( 2 ), which were characterized as thiodiketopiperazine marine natural products isolated from the deep-sea-derived fungus Epicoccum nigrum SD-388. For the flexible compound 2 , we compared various conformational sampling approaches, including an assessment of the quality of relative energies within the obtained ensembles. We demonstrated the critical role of dispersion correction within DFT computations to precisely account for weak non-bonded intramolecular interactions. By integrating anisotropic NMR analysis, chemical shifts, electronic circular dichroism, and DFT computations, we determined the absolute configurations and conformational ensembles for 1 and 2 , respectively, highlighting the significance of the intramolecular methyl–π interaction in stabilizing one of the conformers. Our study introduces new strategies to address conformational flexibility in the stereochemical elucidation of challenging organic molecules.

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Historical genomic variation of Eurasian otters (Lutra lutra) in Britain, from hunting trophies - Sarah J. du Plessis; Nuno F. Martins; Xin Sun; Sarah S. T. Mak; David W. G. Stanton; Klaus-Peter Koepfli; Elizabeth A. Chadwick; M. P. Thomas Gilbert; Frank Hailer (Conservation Genetics Resources, 2025)
Genomic data from historical specimens can provide insights into populations and processes no longer evident from modern samples. Identifying viable sources of historical DNA is key to this. Here we aimed to explore the viability of trophy hunting paws as sources of historical DNA, and to use this data for preliminary analyses to evaluate changes in population structuring over time. We aimed to search for the presence of genomic signals of the putative recent introduction of Eurasian otters ( Lutra lutra ) from Asia to the UK previously identified using modern data, by analysis of two trophy paws from 1929 to 1952. Substantial proportions of endogenous DNA (77–85%) were identified in both samples for which genomic DNA extraction and sequencing was attempted, illustrating the potential of such specimens for historical DNA research. Autosomal variation suggests that the historical specimens cluster closest to modern specimens from Wales, and not with the variation identified in the East of England, putatively associated with the recent introduction of Eurasian otters from Asia. Similarly, the divergent mitochondrial lineage found in modern otters from the East of England and Asia, was not found in the historical British specimens. Although limited inferences can be made from a sample size of two, this preliminary dataset indicates the huge potential of historical trophy paw samples to assess past population genetic dynamics, calling for further research in this area.

Effects of different carbohydrates on growth, hepatic glucose metabolism, and gut microbiome of Florida pompano (Trachinotus carolinus) - Juan F. Paredes; Michael Habte-Tsion; Marty Riche; Sahar Mejri; David Bradshaw; Li Sun Chin; Carlie Perricone; Paul S. Wills (Aquaculture, 2025)

Photothermal functionalized antibacterial packaging film with controllable release capability for fruit preservation - Linpin Luo; Wenqiao Su; Mohamed F. Hassan; Wengang Cai; Meilin Wang; Liang Zhang; Jing Sun; Lunjie Huang; Jianlong Wang (Food Research International, 2025)

Deletion of the Transient Receptor Potential Melastatin 2 Gene Mitigates the 6-Hydroxydopamine-Induced Parkinson’s Disease–Like Pathology - Ana Flavia F. Ferreira; Henning Ulrich; Yasuo Mori; Zhong-Ping Feng; Hong-Shuo Sun; Luiz Roberto Britto (Molecular Neurobiology, 2025)

Tillage reversal of long-term no-till soil increases crop yield while mitigating yield-scaled growing season GHG fluxes in a black Chernozem cropped to barley (Hordeum vulgare L.) - Lei Sun; Yong S. Feng; Miles F. Dyck; Dick Puurveen; Guangwei Wu; Scott X. Chang (Biology and Fertility of Soils, 2025)

Geochemical, U–Pb geochronological, and Hf isotopic characterisation and geological significance of late Caledonian granites in Gushan area of Dagelegou, East Kunlun, China - Y. F. Shi; B. L. Li; H. Li; Z. H. Li; J. Li; Y. M. Sun; Y. T. Liu (Australian Journal of Earth Sciences, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Enhanced aridity in the interior of Asia after the Middle Miocene Climatic Optimum driven by global cooling - Jimin Sun; Weiguo Liu; Brian F. Windley; Longxiao Xu; Tongyan Lü (Global and Planetary Change, 2025)

NTVTOK-ML: Fast surrogate model for neoclassical toroidal viscosity torque calculation in tokamaks based on machine learning methods - X.-T. Yan; N.-N. Bao; C.-Y. Zhao; Y.-W. Sun; Y.-T. Meng; W.-Y. Zhou; N.-Y. Liang; Y.-X. Lu; Y.-F. Liang; B.-N. Wan (Computer Physics Communications, 2025)

Insights into the dynamics of biochemical profile and relative gene expression of cucumber fruits associated with Fusarium spoilage - Muhammad Imran; Hanan A. Khalifa; Zhongke Sun; Muhammad Saqib Bilal; Mohamed Hassan Abd El-Wahed; Kamal A. M. Abo-Elyousr; Esmat F. Ali; Chengwei Li (Journal of Plant Diseases and Protection, 2025)

Excitation functions for fast neutron induced reactions on Al, Zr, In and Au - B. Liu; G. Tian; R. Han; F. Shi; H. Sun; Z. Chen; Z. Zhang; Q. Li; P. Luo (Annals of Nuclear Energy, 2025)

Correction: Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2025)

Editorial– Ocean dynamics in 2024: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Pierre F. J. Lermusiaux; Zhiyu Liu; Yasumasa Miyazawa; et al. (Ocean Dynamics, 2025)

Associations Between Heavy Metal Exposure from Milk and Steroid Hormones in Mothers - Zheng Wang; Caixia Liang; Li Li Shi; Cheng-Sheng Zhu; Shenghang Wang; Shoji F. Nakayama; Teruhiko Kido; Xian Liang Sun; Jiancong Shan (Biological Trace Element Research, 2024)

Metabolic pathway and network analysis integration for discovering the biomarkers in pig feces after a controlled fruit-vegetable dietary intervention - Zhihao Liu; Gloria Solano-Aguilar; Sukla Lakshman; Joseph F. Urban; Mengliang Zhang; Pei Chen; Liangli Lucy Yu; Jianghao Sun (Food Chemistry, 2024)

Insight into the growth and metabolic characteristics of indigenous commercial S. cerevisiae NX11424 at high and low levels of yeast assimilable nitrogen based on metabolomic approach - Yao Lu; Yi Qin; Yue Sun; C.M. Lucy Joseph; Linda F. Bisson; Yuyang Song; Yanlin Liu (Food Microbiology, 2024)

Identification and experimental validation of PYCARD as a crucial PANoptosis-related gene for immune response and inflammation in COPD - Rui Shi; Renwen Liang; Fang Wang; Lueli Wang; Wuyi Zidai; Jie Zhang; Luo Min; Xiaohua Du; Shibo Sun; Chuang Xiao; Chaozhong Li; Xuewu Liang; et al. (Apoptosis, 2024)

Z-Ligustilide restricts rabies virus replication by inducing ferroptosis through the ACSL4-LPCAT3-POR pathway - Jianqing Zhao; Qianruo Wang; Zhenkun Liu; Meixin Sun; Rui Zhou; Zhen F. Fu; Ling Zhao; Ming Zhou (Veterinary Microbiology, 2024)

Innovative digital twin with artificial neural networks for real-time monitoring of structural response: A port structure case study - S.C. Jayasinghe; M. Mahmoodian; A. Sidiq; T.M. Nanayakkara; A. Alavi; Sam Mazaheri; F. Shahrivar; Z. Sun; S. Setunge (Ocean Engineering, 2024)

Flow conditions of the Quaternary Deep-water Current reconstructed by sediment waves in the northeastern South China Sea - Xingxing Wang; Qiliang Sun; Hongbin Wang; Shaoru Yin; Xing Wan; Jie Chen; F. Javier Hernández-Molina (Marine Geology, 2024)

Performances of nitrogen removal by constructed wetlands with different plant species and seasons - F. Sun; Y. Shang; C. Xu; Y. Lv; X. Su; M. Wang; Q. Dong; Y. Xu; M. Li; X. Yin (International Journal of Environmental Science and Technology, 2024)

Food webs in food webs: the micro–macro interplay of multilayered networks - Jake M. Robinson; Andrew D. Barnes; Nicole Fickling; Sofie Costin; Xin Sun; Martin F. Breed (Trends in Ecology & Evolution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Protective Effect of Protocatechuic Aldehyde on Cerebral Ischemia/Reperfusion Injury in Rats through Blood—Brain Barrier Protection - F. He; J. Feng; H. Sun; Y. Xu; H. Yan; X. Song; Y. Wang; X. Li; Q. Lin (Bulletin of Experimental Biology and Medicine, 2024)

LP-18 Simultaneous determination of 5 kinds of virulent mushroom toxinsin human whole blood by ultra performance liquid chromatography- tandem mass spectrometry - L. He; Y. Dong; F. Wang; X. Sun (Toxicology Letters, 2024)

P05-15 Large language models in drug development: deciphering discontinuationc causes to inform future strategies - T. Doktorova; I. Schneider; A. Brigo; J. Pletz; T. Schindler; I. Kulev; J. Sun; E. Rivkin; E. Suekuer; F. Birzele; F. Boess; M. Bopst; et al. (Toxicology Letters, 2024)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

One stone two birds: Endophytes alleviating trace elements accumulation and suppressing soilborne pathogen by stimulating plant growth, photosynthetic potential and defense related gene expression - Muhammad Imran; Zhongke Sun; Kamal A.M Abo-Elyousr; Haider Ali; Munirah F. Aldayel; Chengwei Li (Journal of Hazardous Materials, 2024)

Climate and vegetation change impacts on future conterminous United States water yield - Henrique F. Duarte; John B. Kim; Ge Sun; Steven G. McNulty; Jingfeng Xiao (Journal of Hydrology, 2024)

Multi-Method Formative Evaluation of a Digital Online Grocery Shopping Assistant Among Special Supplemental Nutrition Program for Women, Infants, and Children Participants - Jared T. McGuirt; Elizabeth Anderson Steeves; Jeffrey D. Labban; Angela F. Pfammatter; Kendall Allen; Regis Kopper; Yingcheng Sun; Alison Gustafson (Journal of Nutrition Education and Behavior, 2024)

Metabolomic analysis reveals the interactions between Chinese indigenous and commercial Saccharomyces cerevisiae strains during wine co-fermentations at low YAN concentration - Yue Sun; Yao Lu; C.M. Lucy Joseph; Lingjun Ma; Linda F. Bisson; Yanlin Liu (Food Bioscience, 2024)

Amelioration of habitat since the early Holocene contributed to the origin of agriculture in the farming-pastoral zone of northern China - Xin Jia; Zhiping Zhang; Yonggang Sun; Runqi Jiang; Shuangwen Yi; Wei Chen; Jue Sun; Guoqiang Li; Shuzhi Wang; Enrui Li; Xiaonong Hu; Qingchun Bao; et al. (Science China Earth Sciences, 2024)

Defining weather scenarios for simulation-based assessment of thermal resilience of buildings under current and future climates: A case study in Brazil - Amanda F. Krelling; Roberto Lamberts; Jeetika Malik; Wanni Zhang; Kaiyu Sun; Tianzhen Hong (Sustainable Cities and Society, 2024)

Preclinical Studies on Mechanisms Underlying the Protective Effects of Propranolol in Traumatic Brain Injury: A Systematic Review - James Jae; Yilong Li; Clara Sun; Alison Allan; John Basmaji; Stephanie Chilton; Mohammad Hmidan Simsam; Raymond Kao; Adrian Owen; Neil Parry; Fran Priestap; Bram Rochwerg; et al. (Journal of Neuroimmune Pharmacology, 2024)

Investigating the suitability of online flow cytometry for monitoring full-scale drinking water ozone system disinfection effectiveness - Katherine S. Dowdell; Kirk Olsen; Ernesto F. Martinez Paz; Aini Sun; Jeff Keown; Rebecca Lahr; Brian Steglitz; Andrea Busch; John J. LiPuma; Terese Olson; Lutgarde Raskin (Water Research, 2024)

Rapid Diagnosis of Pneumocystis jirovecii Pneumonia and Respiratory Tract Colonization by Next-Generation Sequencing - Fanfan Xing; Chaowen Deng; Zhendong Luo; Shan Zou; Min Liu; Haiyan Ye; Linlin Sun; Chi-Ching Tsang; Simon K. F. Lo; Susanna K. P. Lau; Patrick C. Y. Woo (Mycopathologia, 2024)
Objectives To describe the epidemiology of Pneumocystis jirovecii pneumonia and colonization diagnosed by next-generation sequencing (NGS) and explore the usefulness of the number of P. jirovecii sequence reads for the diagnosis of P. jirovecii pneumonia. Methods We examined the NGS results for P. jirovecii in respiratory samples collected from patients and analysed their clinical, radiological and microbiological characteristics. Results Among 285 respiratory samples collected over a 12-month period (January to December 2022), P. jirovecii sequences were detected in 56 samples from 53 patients. Fifty (94.3%) of the 53 patients were HIV-negative. Following our case definitions, 37 (69.8%) and 16 (30.2%) of the 53 patients had P. jirovecii infection and colonization respectively. P. jirovecii infection was associated with presence of underlying disease with immunosuppression (94.6% vs 18.8%, P < 0.05), positive serum 1,3-β-D-glucan (41.2% vs 0%, P < 0.01) and higher number of P. jirovecii sequence reads ( P < 0.005). In contrast, P. jirovecii colonization was associated with the male sex (93.8% vs 54.1%, P < 0.01), another definitive infectious disease diagnosis of the respiratory tract (43.8% vs 2.7%, P < 0.001) and higher survival (100% vs 67.6%, P < 0.01). Although P. jirovecii pneumonia was associated with higher number of P. jirovecii reads in respiratory samples, only a sensitivity of 82.14% and a specificity of 68.75% could be achieved. Conclusion Detection of P. jirovecii sequences in respiratory samples has to be interpreted discreetly. A combination of clinical, radiological and laboratory findings is still the most crucial in determining whether a particular case is genuine P. jirovecii pneumonia.

Paleoecology and paleobiogeography of the latest Miocene site of Shuitangba, Zhaotong, China - D.F. Su; J. Kelley; L.J. Flynn; X.P. Ji; C.L. Deng; T. Deng; P. Li; Z. Li; W.J. Sanders; T.A. Stidham; F. Sun; X. Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

The natural history and genotype–phenotype correlations of TMPRSS3 hearing loss: an international, multi-center, cohort analysis - Brett M. Colbert; Cris Lanting; Molly Smeal; Susan Blanton; Derek M. Dykxhoorn; Pei-Ciao Tang; Richard L. Getchell; Hedwig Velde; Mirthe Fehrmann; Ryan Thorpe; Prem Chapagain; Heidy Elkhaligy; et al. (Human Genetics, 2024)
TMPRSS3 -related hearing loss presents challenges in correlating genotypic variants with clinical phenotypes due to the small sample sizes of previous studies. We conducted a cross-sectional genomics study coupled with retrospective clinical phenotype analysis on 127 individuals. These individuals were from 16 academic medical centers across 6 countries. Key findings revealed 47 unique TMPRSS3 variants with significant differences in hearing thresholds between those with missense variants versus those with loss-of-function genotypes. The hearing loss progression rate for the DFNB8 subtype was 0.3 dB/year. Post-cochlear implantation, an average word recognition score of 76% was observed. Of the 51 individuals with two missense variants, 10 had DFNB10 with profound hearing loss. These 10 all had at least one of 4 TMPRSS3 variants predicted by computational modeling to be damaging to TMPRSS3 structure and function. To our knowledge, this is the largest study of TMPRSS3 genotype–phenotype correlations. We find significant differences in hearing thresholds, hearing loss progression, and age of presentation, by TMPRSS3 genotype and protein domain affected. Most individuals with TMPRSS3 variants perform well on speech recognition tests after cochlear implant, however increased age at implant is associated with worse outcomes. These findings provide insight for genetic counseling and the on-going design of novel therapeutic approaches.

A low-methane rice with high-yield potential realized via optimized carbon partitioning - Jia Hu; Mathilde Bettembourg; Lihong Xue; Ronggui Hu; Anna Schnürer; Chuanxin Sun; Yunkai Jin; Jens F. Sundström (Science of The Total Environment, 2024)

Editorial – Ocean Dynamics in 2023: overview and thank you to reviewers - Tal Ezer; Antonio Bonaduce; Sandro Carniel; Chabchoub Amin; Ricardo de Camargo; Sheila N. Estrada-Allis; Oliver B. Fringer; Avijit Gangopadhyay; Guoping Gao; Richard J. Greatbatch; Pierre F. J. Lermusiaux; Zhiyu Liu; et al. (Ocean Dynamics, 2024)

What makes a cyanobacterial bloom disappear? A review of the abiotic and biotic cyanobacterial bloom loss factors - Ted D. Harris; Kaitlin L. Reinl; Marzi Azarderakhsh; Stella A. Berger; Manuel Castro Berman; Mina Bizic; Ruchi Bhattacharya; Sarah H. Burnet; Jacob A. Cianci-Gaskill; Lisette N. de Senerpont Domis; Inge Elfferich; K. Ali Ger; et al. (Harmful Algae, 2024)

Improving growth, omega-3 contents, and disease resistance of Asian seabass: status of a 20-year family-based breeding program - G. H. Yue; L. Wang; F. Sun; Z. T. Yang; J. Wong; Y. F. Wen; H. Y. Pang; M. Lee; S. T. Yeo; B. Liang; K. Chen; H. S. Lim; et al. (Reviews in Fish Biology and Fisheries, 2024)

FKBP51-Hsp90 Interaction-Deficient Mice Exhibit Altered Endocrine Stress Response and Sex Differences Under High-Fat Diet - Lisha Wang; Jakub Wojcieszak; Rajnish Kumar; Zhe Zhao; Xuelian Sun; Shaoxun Xie; Bengt Winblad; Pavel F. Pavlov (Molecular Neurobiology, 2024)
FK506-binding protein 51 kDa (FKBP51), encoded by Fkbp5 gene, gained considerable attention as an important regulator of several aspects of human biology including stress response, metabolic dysfunction, inflammation, and age-dependent neurodegeneration. Its catalytic peptidyl-prolyl isomerase (PPIase) activity is mediated by the N-terminal FK506-binding (FK1) domain, whereas the C-terminal tetratricopeptide motif (TPR) domain is responsible for FKBP51 interaction with molecular chaperone heat shock protein 90 (Hsp90). To understand FKBP51-related biology, several mouse models have been created. These include Fkbp5 complete and conditional knockouts, overexpression, and humanized models. To dissect the role of FKBP51-Hsp90 interaction in FKBP51 biology, we have created an interaction-deficient mouse ( Fkbp5 TPRmut ) by introducing two-point mutations in the TPR domain of FKBP51. FKBP51-Hsp90 interaction-deficient mice are viable, fertile and show Mendelian inheritance. Intracellular association of FKBP51 with Hsp90 is significantly reduced in homozygous mutants compared to wild-type animals. No behavioral differences between genotypes were seen at 2 months of age, however, sex-dependent differences were detected in Y-maze and fear conditioning tests at the age of 12 months. Moreover, we have found a significant reduction in plasma levels of corticosterone and adrenocorticotropic hormone in Fkbp5 TPRmut mice after acute stress. In contrast to Fkbp5 knockout mice, females of Fkbp5 TPRmut showed increased body weight gain under high-fat diet treatment. Our data confirm the importance of FKBP51-Hsp90 interactions for stress-related endocrine signaling. Also, Fkbp5 TPRmut mice can serve as a useful in vivo tool to discriminate between Hsp90-dependent and independent functions of FKBP51.

New early Oligocene age for the Mouding Basin, Southwestern China: Source and paleoenvironment - Xilin Sun; Wenna Ding; Klaudia F. Kuiper; Yuntao Tian; Zengjie Zhang; Rujun Guo; Jan R. Wijbrans (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Chlorella vulgaris microalgae derived blends in micro gas turbine engines: A comprehensive environmental impact analysis for highway vehicle applications - Hanzheng Sun; A Anderson; Mohammed F. Albeshr; Abdulwahed Fahad Alrefaei; Quynh Hoang Le; Beata Gavurová; Rajasree Shanmuganathan (Fuel, 2024)

Urban greenspaces shape soil protist communities in a location-specific manner - Hua-Yuan Shangguan; Stefan Geisen; Zhi-Peng Li; Hai-Feng Yao; Gang Li; Martin F. Breed; Stefan Scheu; Xin Sun (Environmental Research, 2024)

A bibliometric analysis of the toxicity research of carbon nanomaterials - M. Han; Y. Lei; F. X. Yang; H. F. Sun (International Journal of Environmental Science and Technology, 2024)

Clumped isotope reordering kinetics in strontianite and witherite: Experiments and first-principles simulations - Zeyang Sun; Saul Perez-Beltran; Wasif Zaheer; William F. Defliese; Sarbajit Banerjee; Ethan L. Grossman (Earth and Planetary Science Letters, 2023)

Surface subsidence and its reclamation of a coal mine locating at the high groundwater table, China - Z. H. Wang; S. X. Wu; J. L. Li; W. C. Sun; Z. F. Wang; P. J. Liu (International Journal of Environmental Science and Technology, 2023)

Assessing the genetic diversity of Nymphoides peltata in the native and adventive range using microsatellite markers - Nicholas P. Tippery; Nathan E. Harms; Matthew F. Purcell; Sun Hee Hong; Patrick Häfliger; Katelin Killoy; Ashley L. Wolfe; Ryan A. Thum (Biological Invasions, 2023)

Iodine-to-calcium ratios in deep-sea scleractinian and bamboo corals - Yun-Ju Sun; Laura F. Robinson; Ian J. Parkinson; Joseph A. Stewart; Wanyi Lu; Dalton S. Hardisty; Qian Liu; James Kershaw; Michèle LaVigne; Tristan J. Horner (Frontiers in Marine Science, 2023)
The distribution of dissolved iodine in seawater is sensitive to multiple biogeochemical cycles, including those of nitrogen and oxygen. The iodine-to-calcium ratio (I/Ca) of marine carbonates, such as bulk carbonate or foraminifera, has emerged as a potential proxy for changes in past seawater oxygenation. However, the utility of the I/Ca proxy in deep-sea corals, natural archives of seawater chemistry with wide spatial coverage and radiometric dating potential, remains unexplored. Here, we present the first I/Ca data obtained from modern deep-sea corals, specifically scleractinian and bamboo corals, collected from the Atlantic, Eastern Pacific, and Southern Oceans, encompassing a wide range of seawater oxygen concentrations (10–280 μmol/kg). In contrast to thermodynamic predictions, we observe higher I/Ca ratios in aragonitic corals (scleractinian) compared to calcitic corals (bamboo). This observation suggests a strong biological control during iodate incorporation into deep-sea coral skeletons. For the majority of scleractinian corals, I/Ca exhibits a covariation with local seawater iodate concentrations, which is closely related to seawater oxygen content. Scleractinian corals also exhibit notably lower I/Ca below a seawater oxygen threshold of approximately 160 μmol/kg. In contrast, no significant differences in I/Ca are found among bamboo corals across the range of oxygen concentrations encountered (15–240 μmol/kg). In the North Atlantic, several hydrographic factors, such as temperature and/or salinity, may additionally affect coral I/Ca. Our results highlight the potential of I/Ca ratios in deep-sea scleractinian corals to serve as an indicator of past seawater iodate concentrations, providing valuable insights into historical seawater oxygen levels.

Degree of urbanization and vegetation type shape soil biodiversity in city parks - Haifeng Yao; Zhipeng Li; Stefan Geisen; Zhihong Qiao; Martin F. Breed; Xin Sun (Science of The Total Environment, 2023)

Coupled sorptive and oxidative antimony(III) removal by iron-modified biochar: Mechanisms of electron-donating capacity and reactive Fe species - Yurong Gao; Hanbo Chen; Zheng Fang; Nabeel Khan Niazi; Kwasi Adusei-Fosu; Jianhong Li; Xing Yang; Zhongzhen Liu; Nanthi S. Bolan; Bin Gao; Deyi Hou; Chenghua Sun; et al. (Environmental Pollution, 2023)

Changes in genetic diversity of Asian seabass in a 20-year breeding program - J. Wong; F. Sun; L. Wang; Z.T. Yang; Y.F. Wen; H.Y. Pang; M. Lee; S.T. Yeo; B. Liang; K. Chen; J.H. Jiang; G.H. Yue (Aquaculture, 2023)

One sample multi-point calibration curve as a novel approach for quantitative LC-MS analysis: The quantitation of six aflatoxins in milk and oat-based milk as an example - Feifei Sun; Peixu Wu; Mohamed F. Abdallah; Haiguang Tan; Yi Li; Shupeng Yang (Food Chemistry, 2023)

The multi-year effect of different agroecological practices on soil nematodes and soil respiration - Feng Sun; Sékou F. M. Coulibaly; Nathalie Cheviron; Christian Mougin; Mickaël Hedde; Pierre-Alain Maron; Sylvie Recous; Jean Trap; Cécile Villenave; Matthieu Chauvat (Plant and Soil, 2023)

Characterisation of laminarin extracted from brown seaweed Laminaria digitata, using optimized ultrasound- and ultrafiltration-assisted extraction method - Xianglu Zhu; Laura Healy; Janith Wanigasekara; Ming Zhao; Ramesh Babu Padamati; Shanmugapriya Karuppusamy; James F. Curtin; Saravana Periaswamy Sivagnanam; Dilip K. Rai; Da-Wen Sun; Brijesh K. Tiwari (Algal Research, 2023)

The isotope geochemistry of host rocks of the late Archean Guandi and Banshigou banded iron formations, southern Jilin Province: temporal and tectonic significance - J-L. Liu; F-Y. Sun; Y-H Zhou (Australian Journal of Earth Sciences, 2023)

Verification of gene function and interaction protein of PhPIF4 - Y.J. Zhang; L.J. Renzeng; J.W. Zhang; W.J. Guo; F. Lan; P.S. Ding; J.X. Sun (South African Journal of Botany, 2023)

Editorial preface to special issue: Cenozoic tectonics and paleoclimate in Inner Asia: From case studies to climatic modelling - Jimin Sun; Wenjiao Xiao; Brian F. Windley; Yongyun Hu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Late Eocene stepwise seawater retreat from the Pamir-Tian Shan convergence zone (Alay Valley) in the western Tarim Basin, China - Jimin Sun; Jingeng Sha; Brian F. Windley; Zhiliang Zhang; Bihong Fu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Target sequence capture data shed light on the deeper evolutionary relationships of subgenus Chamaecerasus in Lonicera (Caprifoliaceae) - Qing-Hui Sun; Diego F. Morales-Briones; Hong-Xin Wang; Jacob B. Landis; Jun Wen; Hua-Feng Wang (Molecular Phylogenetics and Evolution, 2023)

Assessing decarbonization pathways of China’s heavy-duty trucks in a well-to-wheels perspective - Xingyu Xue; Jianxin Li; Xin Sun; Amir F. N. Abdul-Manan; Sha Du; Huanran Liu; Shujie Xu; Mingnan Zhao (The International Journal of Life Cycle Assessment, 2023)

Special issue of Medicinal Chemistry Research in honor of Dr. Nicholas A. Meanwell - John F. Kadow; Kap-Sun Yeung; T. G. Murali Dhar (Medicinal Chemistry Research, 2023)

Volcanic phosphorus supply boosted Mesozoic terrestrial biotas in northern China - Chao Ma; Yanjie Tang; Ross N. Mitchell; Yongfei Li; Shouliang Sun; Jichang Zhu; Stephen F. Foley; Min Wang; Chenyang Ye; Jifeng Ying; Rixiang Zhu (Science Bulletin, 2023)

Cultivation model and deficit irrigation strategy for reducing leakage of bundle sheath cells to CO2, improve 13C carbon isotope, photosynthesis and soybean yield in semi-arid areas - Honglei Ren; Fengyi Zhang; Xiao Zhu; Sobhi F. Lamlom; Xiulin Liu; Xueyang Wang; Kezhen Zhao; Jinsheng Wang; Mingming Sun; Ming Yuan; Yuan Gao; Jiajun Wang; et al. (Journal of Plant Physiology, 2023)

Zoning strategies for managing outbreaks of alien plant pests in the European Union: a review - Hongyu Sun; Jacob C. Douma; Martijn F. Schenk; Roel P. J. Potting; Donato Boscia; Antonio Vicent; Alan MacLeod; Wopke van der Werf (Journal of Pest Science, 2023)
Managing outbreaks of alien plant pests is key to preserving biodiversity and safeguarding crop production. Zoning strategies are applied by plant health authorities to tailor measures to the risk of spread in relation to distance from the outbreak epicentre and the biology of the pest. Here we synthesize information on outbreak management to evaluate the diversity and consistency of such approaches. We collected information on the zoning strategies of 121 outbreaks of 25 plant pests in the European Union (EU). According to the organism’s presence and the measures applied, five zones were distinguished: an infested zone (83% of cases), a buffer zone (76%), a clear-cutting zone (28%), an eradication zone (1%) and a containment zone (1%). Infested zones and buffer zones were adjacent non-overlapping zones, while the clear-cutting zone, eradication zone or containment zone was within either the infested zone or buffer zone. A combination of infested and buffer zones was used in 51% of recorded cases. Measures differed within different zones. Destruction of infested plants in the infested zone was done in 78% of the cases, while surveillance was always applied in the buffer zone. Regulation of an organism at EU level led to a convergence of zoning strategies applied by different member states. Regulations often prescribed the greatest widths used before regulations were issued. Further analyses are needed to explore the efficacy of different strategies including the costs of each strategy. Such analyses should combine insight from practice with bio-economic modelling.

Towards Improving Motor Imagery Brain–Computer Interface Using Multimodal Speech Imagery - Jigang Tong; Zhengxing Xing; Xiaoying Wei; Chao Yue; Enzeng Dong; Shengzhi Du; Zhe Sun; Jordi Solé-Casals; Cesar F. Caiafa (Journal of Medical and Biological Engineering, 2023)
Purpose The brain–computer interface (BCI) based on motor imagery (MI) has attracted extensive interest due to its spontaneity and convenience. However, the traditional MI paradigm is limited by weak features in evoked EEG signal, which often leads to lower classification performance. Methods In this paper, a novel paradigm is proposed to improve the BCI performance, by the speech imaginary combined with silent reading (SR) and writing imagery (WI), instead of imagining the body movements. In this multimodal (imaginary voices and movements) paradigm, the subjects silently read Chinese Pinyin (pronunciation) and imaginarily write the Chinese characters, according to a cue. Results Eight subjects participated in binary classification tasks, by carrying out the traditional MI and the proposed paradigm in different experiments for comparison. 77.03% average classification accuracy was obtained by the new paradigm versus 68.96% by the traditional paradigm. Conclusion The results of experiments show that the proposed paradigm evokes stronger features, which benefits the classification. This work opens a new view on evoking stronger EEG features by multimodal activities/stimuli using specific paradigms for BCI.

SIPN South: six years of coordinated seasonal Antarctic sea ice predictions - François Massonnet; Sandra Barreira; Antoine Barthélemy; Roberto Bilbao; Edward Blanchard-Wrigglesworth; Ed Blockley; David H. Bromwich; Mitchell Bushuk; Xiaoran Dong; Helge F. Goessling; Will Hobbs; Doroteaciro Iovino; et al. (Frontiers in Marine Science, 2023)
Antarctic sea ice prediction has garnered increasing attention in recent years, particularly in the context of the recent record lows of February 2022 and 2023. As Antarctica becomes a climate change hotspot, as polar tourism booms, and as scientific expeditions continue to explore this remote continent, the capacity to anticipate sea ice conditions weeks to months in advance is in increasing demand. Spurred by recent studies that uncovered physical mechanisms of Antarctic sea ice predictability and by the intriguing large variations of the observed sea ice extent in recent years, the Sea Ice Prediction Network South (SIPN South) project was initiated in 2017, building upon the Arctic Sea Ice Prediction Network. The SIPN South project annually coordinates spring-to-summer predictions of Antarctic sea ice conditions, to allow robust evaluation and intercomparison, and to guide future development in polar prediction systems. In this paper, we present and discuss the initial SIPN South results collected over six summer seasons (December-February 2017-2018 to 2022-2023). We use data from 22 unique contributors spanning five continents that have together delivered more than 3000 individual forecasts of sea ice area and concentration. The SIPN South median forecast of the circumpolar sea ice area captures the sign of the recent negative anomalies, and the verifying observations are systematically included in the 10-90% range of the forecast distribution. These statements also hold at the regional level except in the Ross Sea where the systematic biases and the ensemble spread are the largest. A notable finding is that the group forecast, constructed by aggregating the data provided by each contributor, outperforms most of the individual forecasts, both at the circumpolar and regional levels. This indicates the value of combining predictions to average out model-specific errors. Finally, we find that dynamical model predictions (i.e., based on process-based general circulation models) generally perform worse than statistical model predictions (i.e., data-driven empirical models including machine learning) in representing the regional variability of sea ice concentration in summer. SIPN South is a collaborative community project that is hosted on a shared public repository. The forecast and verification data used in SIPN South are publicly available in near-real time for further use by the polar research community, and eventually, policymakers.

Noncomposite concrete deck bracing effects on continuous steel stringer lateral torsional buckling resistance - C. Shawn Sun; Oluwatobi F. Babarinde; Dinesha Kuruppuarachchi; Daniel G. Linzell; Jay A. Puckett; Emmanuel Akintunde (Engineering Structures, 2023)

Experimental study on the adsorption and desorption performance of composite adsorbent activated carbon/calcium chloride - H. Zhao; B. Zhang; Y. Gao; F. Zhang; Y. Sun (International Journal of Environmental Science and Technology, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Hydrothermal alteration and corresponding reservoir significance of the Permian Emeishan basaltic lavas, west Sichuan, China - Y. B. Sun; Y. F. Zhang; A. H. Xi; Y. Tang; B. J. Zhang; S. Q. Pei; R. R. Li; H. Yin; Q. Zeng; H. Z. Qu; R. J. Zhou (Australian Journal of Earth Sciences, 2023)

Forest water-use efficiency: Effects of climate change and management on the coupling of carbon and water processes - Zhiqiang Zhang; Lu Zhang; Hang Xu; Irena F. Creed; Juan A. Blanco; Xiaohua Wei; Ge Sun; Heidi Asbjornsen; Kevin Bishop (Forest Ecology and Management, 2023)

Long-term hydromechanical behaviour of a deep cavity taking into account a simplified sequence of life stages - Y. Sun; H. Wong; B. Pardoen; F. Deleruyelle; N. Dufour (Computers and Geotechnics, 2023)

Bending Deformation and Ultimate Moment Calculation of Screen Pipes in Offshore Sand Control Completion - Yudan Peng; Guangming Fu; Baojiang Sun; Xiaohui Sun; Jiying Chen; Segen F. Estefen (Journal of Marine Science and Engineering, 2023)
Horizontal wells, extended-reach wells, and multi-branch wells were often used to exploit subsea oil and gas efficiently. However, during the sand control screen completion of those wells, the sand control screen pipe was easily deformed. Failure occurred when passing through the bending section due to the large bending section in the wellbore trajectory. A parametric analysis model of the screen pipe was established based on ABAQUS and Python software under pure bending load first. Then, deformation patterns and mechanisms were identified and discussed. The effects of parameters on the screen pipe bending deformation patterns and the ultimate moment were analyzed. Finally, an empirical formula for calculating the ultimate moment of the screen pipe was established. The results showed that the deformation of the screen pipe was complex, and three deformation patterns were related to the hole parameters. Due to an increase in the diameter and number of circumferential and axial holes, the ultimate moment of the screen pipe gradually decreased, and the circumferential holes had a more significant effect on the ultimate moment than the axial holes. The established empirical formula could accurately calculate the ultimate moment of the screen pipe, and the average difference between the formula and numerical simulation results was 3.25%.

Manganous water column in the Tethys Ocean during the Permian-Triassic transition - J. Müller; Y.D. Sun; F. Yang; M. Regelous; M.M. Joachimski (Global and Planetary Change, 2023)

Microbial transformation to remediate mercury pollution: strains isolation and laboratory study - X. Jing; T. Lu; F. Sun; J. Xie; D. Ma; X. Wang; Q. Dong (International Journal of Environmental Science and Technology, 2023)

Boosting NAD ameliorates hematopoietic impairment linked to short telomeres in vivo - Amanda J. Stock; Saipriya Ayyar; Amogh Kashyap; Yunong Wang; Hagai Yanai; Matthew F. Starost; Mayuri Tanaka-Yano; Monica Bodogai; Chongkui Sun; Yajun Wang; Yi Gong; Chandrakala Puligilla; et al. (GeroScience, 2023)
Short telomeres are a defining feature of telomere biology disorders (TBDs), including dyskeratosis congenita (DC), for which there is no effective general cure. Patients with TBDs often experience bone marrow failure. NAD, an essential metabolic coenzyme, is decreased in models of DC. Herein, using telomerase reverse transcriptase null ( Tert −/− ) mice with critically short telomeres, we investigated the effect of NAD supplementation with the NAD precursor, nicotinamide riboside (NR), on features of health span disrupted by telomere impairment. Our results revealed that NR ameliorated body weight loss in Tert −/− mice and improved telomere integrity and telomere dysfunction-induced systemic inflammation. NR supplementation also mitigated myeloid skewing of Tert −/− hematopoietic stem cells. Furthermore, NR alleviated villous atrophy and inflammation in the small intestine of Tert −/− transplant recipient mice. Altogether, our findings support NAD intervention as a potential therapeutic strategy to enhance aspects of health span compromised by telomere attrition.

Evolution of diagenetic fluids in the deeply buried, upper Ediacaran Dengying Formation, Central Sichuan Basin, China - Y. J. Hu; C. F. Cai; Y. Li; R. Zhou; Y. J. Tang; J. F. Hu; F. C. Lu; P. Sun (Australian Journal of Earth Sciences, 2023)

Novel one-point calibration strategy for high-throughput quantitation of microcystins in freshwater using LC-MS/MS - Huiyan Zhang; Yanshen Li; Mohamed F. Abdallah; Haiguang Tan; Jianxun Li; Shuyan Liu; Rong Zhang; Feifei Sun; Yi Li; Shupeng Yang (Science of The Total Environment, 2023)

Variations of multiple gaseous emissions associated with the great Sumatra earthquakes in 2004 and 2005 - Y. Cui; C. Zheng; L. Jiang; J. Huang; F. Sun; Z. Zou; J. Du (Chemical Geology, 2023)

A deleterious Sar1c variant in rice inhibits export of seed storage proteins from the endoplasmic reticulum - Xiuhao Bao; Yongfei Wang; Yanzhou Qi; Cailin Lei; Yunlong Wang; Tian Pan; Mingzhou Yu; Yu Zhang; Hongming Wu; Pengcheng Zhang; Yi Ji; Hang Yang; et al. (Plant Molecular Biology, 2023)

Hypoxia-Induced Neurite Outgrowth Involves Regulation Through TRPM7 - Ekaterina Turlova; Delphine Ji; Marielle Deurloo; Raymond Wong; Andrea Fleig; F. David Horgen; Hong-Shuo Sun; Zhong-Ping Feng (Molecular Neurobiology, 2023)

Kinetics of nitrous oxide production from ammonia oxidation in the Eastern Tropical North Pacific - Claudia Frey; Xin Sun; Laura Szemberski; Karen L. Casciotti; Emilio Garcia‐Robledo; Amal Jayakumar; Colette L. Kelly; Moritz F. Lehmann; Bess B. Ward (Limnology and Oceanography, 2023)
Marine oxygen‐deficient zones represent a natural source of nitrous oxide (N 2 O), a potent greenhouse gas and ozone‐depleting agent. To investigate controls on N 2 O production, the responses of ammonia oxidation (AO) to nitrite () and N 2 O with respect to oxygen (O 2 ), ammonium () and concentrations were evaluated using tracer incubations in the Eastern Tropical North Pacific. Within the oxycline, additions of and O 2 stimulated N 2 O production according to Michaelis–Menten kinetics, indicating that both substrates were limiting, and that N 2 O production, even if the exact mechanisms remain uncertain, is mediated by predictable kinetics. Low half‐saturation constants for (12–28 nM) and O 2 (460 ± 130 nM) during N 2 O production indicate that AO communities are well adapted to low concentrations of both substrates. Hybrid N 2 O formation (i.e., from one and one unlabeled nitrogen (N) source, e.g., , NO) accounted for ~ 90% of the N 2 O production from and was robust across the different O 2 , , and conditions. Lack of response to variable substrate concentrations implies that the unlabeled N source was not limiting for N 2 O production. Although both O 2 and were key modulators of N 2 O production rates, N 2 O yield (N 2 O produced per produced) seemed to be controlled solely by O 2 . The N 2 O yield increased when O 2 concentrations dropped below the half‐saturation concentration for AO to ( μ M), the range where production decreased faster than N 2 O production. Our study shows that O 2 control on N 2 O yield from AO is robust across stations and depths.

The early–middle Silurian Delite monzogranite and quartz syenite, East Kunlun Orogenic Belt, NW China: petrogenesis and implications for tectonic evolution of the Proto‑Tethys - F. C. Wang; J. Y. Li; Y. J. Shen; T. Tian; Y. Qian; F. Y. Sun; H. X. Wang (Australian Journal of Earth Sciences, 2023)

Middle Miocene paleoenvironmental change and paleoelevation of the Lunpola Basin, Central Tibet - Jimin Sun; Jianguo Li; Weiguo Liu; Brian F. Windley; Alex Farnsworth; Chunsheng Jin; Zhiliang Zhang; Wenjiao Xiao (Global and Planetary Change, 2023)

Screening Hoffman-type metal organic frameworks for efficient C2H2/CO2 separation - Wushuang Lou; Jiahao Li; Wanqi Sun; Yongqi Hu; Lingyao Wang; Rodrigo F. Neumann; Mathias Steiner; Zonglin Gu; Binquan Luan; Yuanbin Zhang (Chemical Engineering Journal, 2023)

Structural characterization of SARS-CoV-2 dimeric ORF9b reveals potential fold-switching trigger mechanism - Xiyue Jin; Xue Sun; Yan Chai; Yu Bai; Ying Li; Tianjiao Hao; Jianxun Qi; Hao Song; Catherine C. L. Wong; George F. Gao (Science China Life Sciences, 2023)

Chlorophyll fluorescence and grain filling characteristic of wheat (Triticum aestivum L.) in response to nitrogen application level - Hafeez Noor; Min Sun; Hussah I. M. Algwaiz; Alam Sher; Sajid Fiaz; KOTB A. Attia; Shabir Hussain Wani; Muneera D. F. AlKahtani; Latifa Al Husnain; Wen Lin; Zhiqiang Gao (Molecular Biology Reports, 2022)

Patient ethnicity and cascade genetic testing: a descriptive study of a publicly funded hereditary cancer program - Eryn F. Braley; Angela C. Bedard; Jennifer Nuk; Quan Hong; James E. J. Bedard; Sophie Sun; Kasmintan A. Schrader (Familial Cancer, 2022)

Demographic composition, not demographic diversity, predicts biomass and turnover across temperate and tropical forests - Jessica F. Needham; Daniel J. Johnson; Kristina J. Anderson‐Teixeira; Norman Bourg; Sarayudh Bunyavejchewin; Nathalie Butt; Min Cao; Dairon Cárdenas; Chia‐Hao Chang‐Yang; Yu‐Yun Chen; George Chuyong; Handanakere S. Dattaraja; et al. (Global Change Biology, 2022)
The growth and survival of individual trees determine the physical structure of a forest with important consequences for forest function. However, given the diversity of tree species and forest biomes, quantifying the multitude of demographic strategies within and across forests and the way that they translate into forest structure and function remains a significant challenge. Here, we quantify the demographic rates of 1961 tree species from temperate and tropical forests and evaluate how demographic diversity (DD) and demographic composition (DC) differ across forests, and how these differences in demography relate to species richness, aboveground biomass (AGB), and carbon residence time. We find wide variation in DD and DC across forest plots, patterns that are not explained by species richness or climate variables alone. There is no evidence that DD has an effect on either AGB or carbon residence time. Rather, the DC of forests, specifically the relative abundance of large statured species, predicted both biomass and carbon residence time. Our results demonstrate the distinct DCs of globally distributed forests, reflecting biogeography, recent history, and current plot conditions. Linking the DC of forests to resilience or vulnerability to climate change, will improve the precision and accuracy of predictions of future forest composition, structure, and function.

The kinetics of ammonium uptake and oxidation across the Southern Ocean - Mhlangabezi Mdutyana; Xin Sun; Jessica M. Burger; Raquel F. Flynn; Shantelle Smith; Natasha R. van Horsten; Alakendra N. Roychoudhury; Hélène Planquette; Eva Bucciarelli; Sandy J. Thomalla; Bess B. Ward; Sarah E. Fawcett (Limnology and Oceanography, 2022)
Central to the Southern Ocean's role in setting atmospheric CO 2 is the seasonal alternation between upward mixing of nutrients and their subsequent consumption by phytoplankton. Active nutrient cycling within the mixed layer, including the release of ammonium (NH 4 + ) and its removal by phytoplankton and nitrifiers, also affects Southern Ocean CO 2 drawdown, yet remains poorly understood. We conducted kinetics experiments across the Southern Ocean south of Africa to investigate the dependence of NH 4 + uptake (summer, winter) and oxidation (winter) on NH 4 + concentration. NH 4 + uptake followed a Michaelis–Menten function in both seasons, with the maximum rate ( V max ) decreasing poleward, apparently controlled mainly by light in winter and temperature in summer. The half‐saturation constant ( K m ) increased poleward with increasing ambient NH 4 + ([NH 4 + ] amb ) and was threefold higher in winter (150–405 nM) than in summer (41–115 nM), suggesting that summertime phytoplankton are adapted to low‐NH 4 + conditions while winter communities typically receive a higher NH 4 + supply. NH 4 + oxidation showed a high affinity for NH 4 + ( K m = 28–137 nM), suggesting a dominant role for ammonia‐oxidizing archaea, and followed a Michaelis–Menten curve only when [NH 4 + ] amb was ≤ 90 nM. V max was near‐constant across the region regardless of [NH 4 + ] amb , temperature, or light. From coincident mixed‐layer NH 4 + oxidation and iron measurements, we hypothesize that iron availability may (co‐)limit the V max of NH 4 + oxidation. If verified, this suggestion has implications for models that parameterize nitrification as a linear function of [NH 4 + ] amb . Additionally, iron depletion may limit the role of mixed‐layer nitrification, which is dominant in the winter Southern Ocean, in offsetting phytoplankton CO 2 drawdown annually.

The Status of Iodine Nutrition after Removing Iodized Salt in High Water Iodine Regions: a Cross-sectional Study in China - J. Yao; W. Zhang; J. Wang; K. Wang; C. Lv; Z. Zhang; X. Chen; Y. Chen; W. Jiang; J. Niu; F. Song; P. Liu; et al. (Biological Trace Element Research, 2022)

Review of Mercury’s dynamic magnetosphere: Post-MESSENGER era and comparative magnetospheres - Weijie Sun; Ryan M. Dewey; Sae Aizawa; Jia Huang; James A. Slavin; Suiyan Fu; Yong Wei; Charles F. Bowers (Science China Earth Sciences, 2022)
This review paper summarizes the research of Mercury’s magnetosphere in the Post-MESSENGER era and compares its dynamics to those in other planetary magnetospheres, especially to those in Earth’s magnetosphere. This review starts by introducing the planet Mercury, including its interplanetary environment, magnetosphere, exosphere, and conducting core. The frequent and intense magnetic reconnection on the dayside magnetopause, which is represented by the flux transfer event “shower”, is reviewed on how they depend on magnetosheath plasma β and magnetic shear angle across the magnetopause, following by how it contributes to the flux circulation and magnetosphere-surface-exosphere coupling. In the next, Mercury’s magnetosphere under extreme solar events, including the core induction and the reconnection erosion on the dayside magnetosphere, the responses of the nightside magnetosphere, are reviewed. Then, the dawn-dusk properties of the plasma sheet, including the features of the ions, the structure of the current sheet, and the dynamics of magnetic reconnection, are summarized. The last topic is devoted to the particle energization in Mercury’s magnetosphere, which includes the energization of the Kelvin-Helmholtz waves on the magnetopause boundaries, reconnection-generated magnetic structures, and the cross-tail electric field. In each chapter, the last section discusses the open questions related to each topic, which can be considered by the simulations and the future spacecraft mission. We end this paper by summarizing the future BepiColombo opportunities, which is a joint mission of ESA and JAXA and is en route to Mercury.

Petrological and isotopic data from Eocene granites in the Luocang area, South Lhasa terrane, Tibet: implications for the India–Eurasia collision - J.-G. Gao; F. Ding; J.-Q. Lin; Q.-H. Zhu; Y. Sun; X.-G. Xie (Australian Journal of Earth Sciences, 2021)

Petrogenesis and tectonic setting of granitic plutons in the Guaizihu region, North Alxa Block, China: constraints from whole-rock geochemistry, zircon U–Pb ages and Hf isotope compositions - F. Q. Xie; Y. H. Sun; L. D. Wang; J. Y. Cao; W. Z. Xiao; J. H. Wu (Australian Journal of Earth Sciences, 2021)

Morphological traits of reef corals predict extinction risk but not conservation status - Nussaïbah B. Raja; Andreas Lauchstedt; John M. Pandolfi; Sun W. Kim; Ann F. Budd; Wolfgang Kiessling (Global Ecology and Biogeography, 2021)
Aim The current assessment of extinction risk in reef corals by the International Union for Conservation of Nature (IUCN) has been criticized, because coral life‐history traits associated with resilience are not reflected in the conservation status. We aimed to carry out a quantitative assessment of the link between reef coral traits and species extinction risk informed by extinctions of reef corals observed in the fossil record. Location Global. Time period Plio‐Pleistocene and present day. Major taxa studied Scleractinian reef corals. Methods We used morphological traits, phylogenetic information and evidence of extinction during the Plio‐Pleistocene to predict the extinction risk of contemporary reef corals. Our model was trained using 138 Caribbean fossil coral species and an automatic machine learning algorithm. We then used this model to predict the extinction risk of 674 modern coral species. Results Model validation confirmed 77% accuracy in predicting extinction risk of fossil corals. Extinction risk predicted by our model showed a near‐random (57%) match with the IUCN conservation status. Our model also suggested that corals in the Least Concern or Near Threatened categories might be at higher risk of extinction than currently believed. Main conclusions Morphological traits of fossil corals linked to their extinction risk in the Plio‐Pleistocene Caribbean Sea are known to reflect the vulnerability of extant corals. However, the results from our fossil‐calibrated model do not match the IUCN assessment of reef corals, with increased overall extinction risk. This does not necessarily indicate near‐future extinction risk, because fossil extinctions are spread over thousands of years. However, we show the applicability of using fossil data to inform the extinction risk of modern corals and recommend that future assessments of extinction risk of reef corals should consider incorporating the relationship between morphological traits and resilience, calibrated by fossil data, to maximize the utility of the extinction risk assessment.

Intermittent subduction of the Paleo-Tethys Ocean in the middle–late Permian: evidence from the mafic–intermediate intrusive rocks in the East Kunlun Orogenic Belt - J. Sun; Y. Qian; Y. Li; H. Li; S. Tian; F. Sun (Australian Journal of Earth Sciences, 2021)

TRPM7 Mediates Neuronal Cell Death Upstream of Calcium/Calmodulin-Dependent Protein Kinase II and Calcineurin Mechanism in Neonatal Hypoxic-Ischemic Brain Injury - Ekaterina Turlova; Raymond Wong; Baofeng Xu; Feiya Li; Lida Du; Steven Habbous; F. David Horgen; Andrea Fleig; Zhong-Ping Feng; Hong-Shuo Sun (Translational Stroke Research, 2021)

Downregulation of Adhesion Molecule CHL1 in B Cells but Not T Cells of Patients with Major Depression and in the Brain of Mice with Chronic Stress - C. R. Yang; L. Ning; F. H. Zhou; Q. Sun; H. P. Meng; Z. Han; Y. Liu; W. Huang; S. Liu; X. H. Li; B. Zheng; Dong Ming; et al. (Neurotoxicity Research, 2020)

Histopathology, Molecular Identification and Antifungal Susceptibility Testing of Nannizziopsis arthrosporioides from a Captive Cuban Rock Iguana (Cyclura nubila) - Yen-Han Chen; Meng-Jou Chi; Pei-Lun Sun; Pin-Huan Yu; Chen-Hsuan Liu; Jose F. Cano-Lira; Wen-Ta Li (Mycopathologia, 2020)

Using genomic tools to inform management of the Atlantic northern fulmar - Lila Colston-Nepali; Jennifer F. Provencher; Mark L. Mallory; Ryan P. Franckowiak; Zhengxin Sun; Gregory J. Robertson; Vicki L. Friesen (Conservation Genetics, 2020)

COSORE: A community database for continuous soil respiration and other soil‐atmosphere greenhouse gas flux data - Ben Bond‐Lamberty; Danielle S. Christianson; Avni Malhotra; Stephanie C. Pennington; Debjani Sihi; Amir AghaKouchak; Hassan Anjileli; M. Altaf Arain; Juan J. Armesto; Samaneh Ashraf; Mioko Ataka; Dennis Baldocchi; et al. (Global Change Biology, 2020)
Globally, soils store two to three times as much carbon as currently resides in the atmosphere, and it is critical to understand how soil greenhouse gas (GHG) emissions and uptake will respond to ongoing climate change. In particular, the soil‐to‐atmosphere CO 2 flux, commonly though imprecisely termed soil respiration ( R S ), is one of the largest carbon fluxes in the Earth system. An increasing number of high‐frequency R S measurements (typically, from an automated system with hourly sampling) have been made over the last two decades; an increasing number of methane measurements are being made with such systems as well. Such high frequency data are an invaluable resource for understanding GHG fluxes, but lack a central database or repository. Here we describe the lightweight, open‐source COSORE (COntinuous SOil REspiration) database and software, that focuses on automated, continuous and long‐term GHG flux datasets, and is intended to serve as a community resource for earth sciences, climate change syntheses and model evaluation. Contributed datasets are mapped to a single, consistent standard, with metadata on contributors, geographic location, measurement conditions and ancillary data. The design emphasizes the importance of reproducibility, scientific transparency and open access to data. While being oriented towards continuously measured R S , the database design accommodates other soil‐atmosphere measurements (e.g. ecosystem respiration, chamber‐measured net ecosystem exchange, methane fluxes) as well as experimental treatments (heterotrophic only, etc.). We give brief examples of the types of analyses possible using this new community resource and describe its accompanying R software package.

A robust relationship between multidecadal global warming rate variations and the Atlantic Multidecadal Variability - Zhiyu Li; Wenjun Zhang; Fei-Fei Jin; Malte F. Stuecker; Cheng Sun; Aaron F. Z. Levine; Haiming Xu; Chao Liu (Climate Dynamics, 2020)

Urban storage heat flux variability explored using satellite, meteorological and geodata - F. Lindberg; K. F. G. Olofson; T. Sun; C. S. B. Grimmond; C. Feigenwinter (Theoretical and Applied Climatology, 2020)
The storage heat flux (Δ Q S ) is the net flow of heat stored within a volume that may include the air, trees, buildings and ground. Given the difficulty of measurement of this important and large flux in urban areas, we explore the use of Earth Observation (EO) data. EO surface temperatures are used with ground-based meteorological forcing, urban morphology, land cover and land use information to estimate spatial variations of Δ Q S in urban areas using the Element Surface Temperature Method (ESTM). First, we evaluate ESTM for four “simpler” surfaces. These have good agreement with observed values. ESTM coupled to SUEWS (an urban land surface model) is applied to three European cities (Basel, Heraklion, London), allowing EO data to enhance the exploration of the spatial variability in Δ Q S . The impervious surfaces (paved and buildings) contribute most to Δ Q S . Building wall area seems to explain variation of Δ Q S most consistently. As the paved fraction increases up to 0.4, there is a clear increase in Δ Q S . With a larger paved fraction, the fraction of buildings and wall area is lower which reduces the high values of Δ Q S .

The association between dioxins and steroid hormones in general adult males: a cross-sectional study in an e-waste region of China - Li Li Shi; Mei Qin Wang; Shoji F. Nakayama; Chau-Ren Jung; Yue Hua Wang; Jing Jian Dong; Chao Chen Ma; Teruhiko Kido; Xian Liang Sun; Hao Feng (Environmental Science and Pollution Research, 2020)

Automated volcanic hot-spot detection based on FY-4A/AGRI infrared data - S. S. Chu; L. Zhu; H. F. Sun; Q. W. Li; X. R. Zhang; T. T. Chen; L. Qiao; W. R. Zhu; D. X. Zhao; Y. H. Zhang (International Journal of Remote Sensing, 2020)

Utilization of pre-existing competent and barren quartz veins as hosts to later orogenic gold ores at Huangjindong gold deposit, Jiangnan Orogen, southern China - Liang Zhang; David I. Groves; Li-Qiang Yang; Si-Chen Sun; Roberto F. Weinberg; Jiu-Yi Wang; Sheng-Gang Wu; Lei Gao; Lan-Ling Yuan; Rong-Hua Li (Mineralium Deposita, 2020)

Aphid resistance in Capsicum maps to a locus containing LRR-RLK gene analogues - Mengjing Sun; Roeland E. Voorrips; Wendy van’t Westende; Martijn van Kaauwen; Richard G. F. Visser; Ben Vosman (Theoretical and Applied Genetics, 2020)
Key message A QTL for aphid resistance on pepper chromosome 2 was identified and validated. This QTL affects aphid survival and reproduction, and was fine mapped to a locus containing LRR-RLK analogues. Abstract Myzus persicae is one of the most threatening insect pests that adversely affects pepper ( Capsicum ) cultivation. Resistance to aphids was previously identified in Capsicum baccatum . This study aimed at elucidating the genetics of aphid resistance in C. baccatum . A QTL analysis was carried out for M. persicae resistance in an F 2 population derived from an intraspecific cross between a highly resistant plant and a susceptible plant. Survival and reproduction were used as resistance parameters. Interval mapping detected two QTLs affecting aphid survival ( Rmpas-1 ) and reproduction ( Rmprp-1 ), respectively, both localized in the same area and sharing the same top marker on chromosome 2. Use of this marker as co-factor in multiple-QTL mapping analysis revealed a second, minor QTL ( Rmprp-2 ) only affecting aphid reproduction, on chromosome 4. Fine mapping confirmed the effects of Rmpas-1 and Rmprp-1 and narrowed the major QTL Rmprp-1 down to a genomic region of 96 kb which is predicted to encode four analogues of resistance genes of the receptor-like kinase family containing a leucine-rich repeat domain (LRR-RLKs). This work provides not only initial information for breeding aphid-resistant pepper varieties, but also forms the basis for future molecular analysis of gene(s) involved in aphid resistance.

Pupillary light reflex circuits in the macaque monkey: the preganglionic Edinger–Westphal nucleus - Paul J. May; Wensi Sun; Nicholas F. Wright; Jonathan T. Erichsen (Brain Structure and Function, 2020)
The motor outflow for the pupillary light reflex originates in the preganglionic motoneuron subdivision of the Edinger–Westphal nucleus (EWpg), which also mediates lens accommodation. Despite their importance for vision, the morphology, ultrastructure and luminance-related inputs of these motoneurons have not been fully described in primates. In macaque monkeys, we labeled EWpg motoneurons from ciliary ganglion and orbital injections. Both approaches indicated preganglionic motoneurons occupy an EWpg organized as a unitary, ipsilateral cell column. When tracers were placed in the pretectal complex, labeled terminals targeted the ipsilateral EWpg and reached contralateral EWpg by crossing both above and below the cerebral aqueduct. They also terminated in the lateral visceral column, a ventrolateral periaqueductal gray region containing neurons projecting to the contralateral pretectum. Combining olivary pretectal and ciliary ganglion injections to determine whether a direct pupillary light reflex projection is present revealed a labeled motoneuron subpopulation that displayed close associations with labeled pretectal terminal boutons. Ultrastructurally, this subpopulation received synaptic contacts from labeled pretectal terminals that contained numerous clear spherical vesicles, suggesting excitation, and scattered dense-core vesicles, suggesting peptidergic co-transmitters. A variety of axon terminal classes, some of which may serve the near response, synapsed on preganglionic motoneurons. Quantitative analysis indicated that pupillary motoneurons receive more inhibitory inputs than lens motoneurons. To summarize, the pupillary light reflex circuit utilizes a monosynaptic, excitatory, bilateral pretectal projection to a distinct subpopulation of EWpg motoneurons. Furthermore, the interconnections between the lateral visceral column and olivary pretectal nucleus may provide pretectal cells with bilateral retinal fields.

Time and laser ranging: a window of opportunity for geodesy, navigation, and metrology - P. Exertier; A. Belli; E. Samain; W. Meng; H. Zhang; K. Tang; A. Schlicht; U. Schreiber; U. Hugentobler; I. Prochàzka; X. Sun; J. F. McGarry; et al. (Journal of Geodesy, 2019)

Refugia under threat: Mass bleaching of coral assemblages in high‐latitude eastern Australia - Sun W. Kim; Eugenia M. Sampayo; Brigitte Sommer; Carrie A. Sims; Maria del C. Gómez‐Cabrera; Steve J. Dalton; Maria Beger; Hamish A. Malcolm; Renata Ferrari; Nicola Fraser; Will F. Figueira; Stephen D. A. Smith; et al. (Global Change Biology, 2019)
Environmental anomalies that trigger adverse physiological responses and mortality are occurring with increasing frequency due to climate change. At species' range peripheries, environmental anomalies are particularly concerning because species often exist at their environmental tolerance limits and may not be able to migrate to escape unfavourable conditions. Here, we investigated the bleaching response and mortality of 14 coral genera across high‐latitude eastern Australia during a global heat stress event in 2016. We evaluated whether the severity of assemblage‐scale and genus‐level bleaching responses was associated with cumulative heat stress and/or local environmental history, including long‐term mean temperatures during the hottest month of each year (SST LTMAX ), and annual fluctuations in water temperature (SST VAR ) and solar irradiance (PARZ VAR ). The most severely‐bleached genera included species that were either endemic to the region ( Pocillopora aliciae ) or rare in the tropics (e.g. Porites heronensis ). Pocillopora spp., in particular, showed high rates of immediate mortality. Bleaching severity of Pocillopora was high where SST LTMAX was low or PARZ VAR was high, whereas bleaching severity of Porites was directly associated with cumulative heat stress. While many tropical Acropora species are extremely vulnerable to bleaching, the Acropora species common at high latitudes, such as A. glauca and A. solitaryensis , showed little incidence of bleaching and immediate mortality. Two other regionally‐abundant genera, Goniastrea and Turbinaria , were also largely unaffected by the thermal anomaly. The severity of assemblage‐scale bleaching responses was poorly explained by the environmental parameters we examined. Instead, the severity of assemblage‐scale bleaching was associated with local differences in species abundance and taxon‐specific bleaching responses. The marked taxonomic disparity in bleaching severity, coupled with high mortality of high‐latitude endemics, point to climate‐driven simplification of assemblage structures and progressive homogenisation of reef functions at these high‐latitude locations.

Crouzon syndrome mouse model exhibits cartilage hyperproliferation and defective segmentation in the developing trachea - Elizabeth A. Hines; Mary-Kayt N. Jones; Julie F. Harvey; Chad Perlyn; David M. Ornitz; Xin Sun; Jamie M. Verheyden (Science China Life Sciences, 2019)

New Molecular Markers Distinguishing Fonsecaea Agents of Chromoblastomycosis - Gabriela X. Schneider; Renata R. Gomes; Amanda Bombassaro; Kassiely Zamarchi; Morgana F. Voidaleski; Flávia F. Costa; Aniele C. R. Leão; Bruna J. F. S. Lima; Bruna S. Soley; Israella R. Colombo; Giovanna Z. Cândido; Mohammad J. Najafzadeh; et al. (Mycopathologia, 2019)

The Difference of Litter Decay, Litter- and Sediment-Associated Hydrolytic Enzymes between Brackish and Freshwater Tidal Marshes - Weifang Hu; Linhai Zhang; Derrick Y. F. Lai; Jintao Gao; Zhigao Sun; Chuan Tong; Yuehmin Chen; Congsheng Zeng (Estuaries and Coasts, 2019)

Global Observing Needs in the Deep Ocean - Lisa A. Levin; Brian J. Bett; Andrew R. Gates; Patrick Heimbach; Bruce M. Howe; Felix Janssen; Andrea McCurdy; Henry A. Ruhl; Paul Snelgrove; Karen I. Stocks; David Bailey; Simone Baumann-Pickering; et al. (Frontiers in Marine Science, 2019)

Parasites of coral reef fish larvae: its role in the pelagic larval stage - B. Duong; S. P. Blomberg; T. H. Cribb; P. F. Cowman; A. M. Kuris; M. I. McCormick; R. R. Warner; D. Sun; A. S. Grutter (Coral Reefs, 2019)

Characterization of the complete plastome of western red cedar, Thuja plicata (Cupressaceae) - Kole F. Adelalu; Xiao-Jian Qu; Yan-Xia Sun; Tao Deng; Hang Sun; Heng-Chang Wang (Conservation Genetics Resources, 2019)

Numerical Modeling and Simulation of Shale-Gas Transport with Geomechanical Effect - Mohamed F. El-Amin; Jisheng Kou; Shuyu Sun (Transport in Porous Media, 2019)

Condensin controls mitotic chromosome stiffness and stability without forming a structurally contiguous scaffold - Mingxuan Sun; Ronald Biggs; Jessica Hornick; John F. Marko (Chromosome Research, 2018)

Modification of PPTA-based polymeric waste and adsorption properties for metal ions - J. J. Gao; R. J. Qu; S. S. Li; F. W. Pan; X. H. Jia; C. M. Sun; Y. Zhang; Q. L. Ma; C. X. Li (International Journal of Environmental Science and Technology, 2018)

Advances in research on the use of biochar in soil for remediation: a review - Eric F. Zama; Brian J. Reid; Hans Peter H. Arp; Guo-Xin Sun; Hai-Yan Yuan; Yong-Guan Zhu (Journal of Soils and Sediments, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Surge impact behavior of granular flows: effects of water content - G. G. D. Zhou; D. Song; C. E. Choi; A. Pasuto; Q. C. Sun; D. F. Dai (Landslides, 2018)

Identifying water resources management strategies in adaptation to climate change under uncertainty - J. Sun; Y. P. Li; X. W. Zhuang; S.W. Jin; G. H. Huang; R. F. Feng (Mitigation and Adaptation Strategies for Global Change, 2018)

Endovascular Biopsy: In Vivo Cerebral Aneurysm Endothelial Cell Sampling and Gene Expression Analysis - Daniel L. Cooke; David B. McCoy; Van V. Halbach; Steven W. Hetts; Matthew R. Amans; Christopher F. Dowd; Randall T. Higashida; Devon Lawson; Jeffrey Nelson; Chih-Yang Wang; Helen Kim; Zena Werb; et al. (Translational Stroke Research, 2018)

Histochemical distribution of four types of enzymes and mucous cells in the gastrointestinal tract of reared half‐smooth tongue sole Cynoglossus semilaevis - Y. Z. Wang; J. F. Sun; A. J. Lv; S. L. Zhang; Y. Y. Sung; H. Y. Shi; X. C. Hu; S. J. Chen; K. Z. Xing (Journal of Fish Biology, 2018)
The histochemical distribution of acid phosphatase (ACP), alkaline phosphatase (ALP), non‐specific esterase (NSE), peroxidase (POD) and mucous‐cell types was evaluated in the gastrointestinal tract of the half‐smooth tongue sole Cynoglossus semilaevis . The enzymes were detected in the entire stretch of the gastrointestinal tract. ACP activity was found in the supranuclear region of enterocytes and the lamina propria of the intestine, as well as the cytoplasm of epithelial cells of the stomach. The staining intensity of ACP in the anterior and posterior intestines was stronger than in the stomach. ALP activity was detected in the striated border of enterocytes and muscularis of the whole intestine, lamina propria and supranuclear cytoplasm of the enterocytes in the anterior intestine, as well as in the blood vessels of the stomach. The staining intensity for ALP in the anterior intestine was stronger than in the posterior segment and the latter was stronger than in the stomach. NSE activity was detected in the cytoplasm of the epithelial cells in the entire gastrointestinal tract, with the anterior intestine showing stronger intensity than the stomach. POD activity was located in the blood cells of the lamina propria of the gastrointestinal tract and the levels in the stomach were similar to the anterior and posterior intestines. Alcian blue (pH 2·5) periodic acid Schiff (AB‐PAS) histochemical results revealed three types of mucous cells in the gastrointestinal tract. Type I cells (PAS+AB‐) were observed among the gastric mucosa columnar cells in the stomach and enterocytes in the basal region of the villi and in the middle and top regions of the intestinal villi. Type II cells (PAS‐AB+) and type III cells (PAS+AB+) were not detected in the stomach but were distributed ubiquitously among enterocytes in the middle and top regions of the intestinal villi.

A comparison of gap-filling approaches for Landsat-7 satellite data - Gaohong Yin; Gregoire Mariethoz; Ying Sun; Matthew F. McCabe (International Journal of Remote Sensing, 2017)

Sex-specific inhibition and stimulation of worker-reproductive transition in a termite - Qian Sun; Kenneth F. Haynes; Jordan D. Hampton; Xuguo Zhou (The Science of Nature, 2017)

Segmental allotetraploidy generates extensive homoeologous expression rewiring and phenotypic diversity at the population level in rice - Yue Sun; Ying Wu; Chunwu Yang; Shuai Sun; Xiuyun Lin; Lixia Liu; Chunming Xu; Jonathan F. Wendel; Lei Gong; Bao Liu (Molecular Ecology, 2017)
Allopolyploidization, that is, concomitant merging and doubling of two or more divergent genomes in a common nucleus/cytoplasm, is known to instantly alter genomewide transcriptome dynamics, a phenomenon referred to as “transcriptomic shock.” However, the immediate effects of transcriptomic alteration in generating phenotypic diversity at the population level remain underinvestigated. Here, we employed the MassARRAY‐based Sequenom platform to assess and compare orthologous, allelic and homoeologous gene expression status in two tissues (leaf and root) of a set of randomly chosen individuals from populations of parental rice subspecies ( indica and japonica ), in vitro “hybrids” (parental mixes), reciprocal F1 hybrids and reciprocal tetraploids at the 5th‐selfed generation (S5). We show that hybridization and whole genome duplication ( WGD ) have opposing effects on allelic and homoeologous expression in the F1 hybrids and tetraploids, respectively. Whereas hybridization exerts strong attenuating effects on allelic expression differences in diploid hybrids, WGD augments the intrinsic parental differences and generates extensive and variable homoeolog content which triggers diversification in expression patterning among the tetraploid plants. Coupled with the vast phenotypic diversity observed among the tetraploid individuals, our results provide experimental evidence in support of the notion that allopolyploidy catalyses rapid phenotypic diversification in higher plants. Our data further suggest that largely stochastic homoeolog content reshuffling rather than alteration in total expression level may be an important feature of evolution in young segmental allopolyploids, which underlies rapid expression diversity at the population level.

Active smoking and survival following breast cancer among African American and non-African American women in the Carolina Breast Cancer Study - Humberto Parada; Xuezheng Sun; Chiu-Kit Tse; Andrew F. Olshan; Melissa A. Troester; Kathleen Conway (Cancer Causes & Control, 2017)

Ablation of BAF170 in Developing and Postnatal Dentate Gyrus Affects Neural Stem Cell Proliferation, Differentiation, and Learning - Tran Tuoc; Ekrem Dere; Konstantin Radyushkin; Linh Pham; Huong Nguyen; Anton B. Tonchev; Guoqiang Sun; Anja Ronnenberg; Yanhong Shi; Jochen F. Staiger; Hannelore Ehrenreich; Anastassia Stoykova (Molecular Neurobiology, 2017)

Age at diagnosis, obesity, smoking, and molecular subtypes in muscle-invasive bladder cancer - Xuezheng Sun; Katherine A. Hoadley; William Y. Kim; Helena Furberg; Andrew F. Olshan; Melissa A. Troester (Cancer Causes & Control, 2017)

Preventive Effects of Poloxamer 188 on Muscle Cell Damage Mechanics Under Oxidative Stress - Sing Wan Wong; Yifei Yao; Ye Hong; Zhiyao Ma; Stanton H. L. Kok; Shan Sun; Michael Cho; Kenneth K. H. Lee; Arthur F. T. Mak (Annals of Biomedical Engineering, 2017)

Statistical treatment for the wet bias in tree-ring chronologies: a case study from the Interior West, USA - Yan Sun; Matthew F. Bekker; R. Justin DeRose; Roger Kjelgren; S.-Y. Simon Wang (Environmental and Ecological Statistics, 2017)

Spatial and temporal variations in prehistoric human settlement and their influencing factors on the south bank of the Xar Moron River, Northeastern China - Xin Jia; Shuangwen Yi; Yonggang Sun; Shuangye Wu; Harry F. Lee; Lin Wang; Huayu Lu (Frontiers of Earth Science, 2017)

Morphogenesis and Gene Mapping of deformed interior floral organ 1 (difo1), a Novel Mutant Associated with Floral Organ Development in Rice - Lianping P. Sun; Yingxin X. Zhang; Peipei P. Zhang; Zhengfu F. Yang; Xiaoxiao X. Zhou; Dandan D. Xuan; Md Habibur H. Rahman; Zihe H. Li; Weixun X. Wu; Xiaodeng D. Zhan; Xihong H. Shen; Ping Yu; et al. (Plant Molecular Biology Reporter, 2017)

One microenvironment does not fit all: heterogeneity beyond cancer cells - Ik Sun Kim; Xiang H.-F. Zhang (Cancer and Metastasis Reviews, 2016)

Suppressive Effects of Copper Sulfate Accumulation on the Spermatogenesis of Rats - J. Y. Liu; X. Yang; X. D. Sun; C. C. Zhuang; F. B. Xu; Y. F. Li (Biological Trace Element Research, 2016)

Transgenerational Inheritance of Paternal Neurobehavioral Phenotypes: Stress, Addiction, Ageing and Metabolism - Ti-Fei Yuan; Ang Li; Xin Sun; Huan Ouyang; Carlos Campos; Nuno B. F. Rocha; Oscar Arias-Carrión; Sergio Machado; Gonglin Hou; Kwok Fai So (Molecular Neurobiology, 2016)

Neuroprotective Effects of a PSD-95 Inhibitor in Neonatal Hypoxic-Ischemic Brain Injury - Baofeng Xu; Ai-Jiao Xiao; Wenliang Chen; Ekaterina Turlova; Rui Liu; Andrew Barszczyk; Christopher L. F. Sun; Ling Liu; Michael Tymianski; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Sedimentary facies analysis and depositional model of gravity-flow deposits of the Yanchang Formation, southwestern Ordos Basin, NW China - F. Liu; X. Zhu; Y. Li; M. Xue; J. Sun (Australian Journal of Earth Sciences, 2016)

Critical Role of the Sphingolipid Pathway in Stroke: a Review of Current Utility and Potential Therapeutic Targets - Na Sun; Richard F. Keep; Ya Hua; Guohua Xi (Translational Stroke Research, 2016)

Silencing of six susceptibility genes results in potato late blight resistance - Kaile Sun; Anne-Marie A. Wolters; Jack H. Vossen; Maarten E. Rouwet; Annelies E. H. M. Loonen; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

Arsenic Speciation by Sequential Extraction from As-Fe Precipitates Formed Under Different Coagulation Conditions - Zhibin Zhang; Jinxiang Li; Cuizhen Sun; Taha F. Marhaba; Wen Zhang; Yanhao Zhang (Water, Air, & Soil Pollution, 2016)

Characterization of Citric Acid-Modified Clam Shells and Application for Aqueous Lead (II) Removal - Cuizhen Sun; Jinwei Qiu; Zhibin Zhang; Taha F. Marhaba; Yanhao Zhang; Wen Zhang (Water, Air, & Soil Pollution, 2016)

A Mixed Micelle Formulation for Oral Delivery of Vitamin K - Feilong Sun; Tessa C. C. Jaspers; Peter M. van Hasselt; Wim E. Hennink; Cornelus F. van Nostrum (Pharmaceutical Research, 2016)

Zircon dating and mineralogy of the Mokong Pan-African magmatic epidote-bearing granite (North Cameroon) - R. Tchameni; F. Sun; D. Dawaï; G. Danra; L. Tékoum; E. Nomo Negue; O. Vanderhaeghe; C. Nzolang; Nguihdama Dagwaï (International Journal of Earth Sciences, 2016)

Linking morphological and functional variability in hand movement and silent reading - Z. Y. Sun; P. Pinel; D. Rivière; A. Moreno; S. Dehaene; J.-F. Mangin (Brain Structure and Function, 2016)

First case of hepatopancreatic necrosis disease in pond‐reared Chinese mitten crab, Eriocheir sinensis , associated with microsporidian - Z Ding; Q Meng; H Liu; S Yuan; F Zhang; M Sun; Y Zhao; M Shen; G Zhou; J Pan; H Xue; W Wang (Journal of Fish Diseases, 2016)
An epidemic of hepatopancreatic necrosis disease ( HPND ) with a high mortality rate (40%–50%) recently occurred in the cultured Chinese mitten crab, Eriocheir sinensis , which is a very important economic crustacean species in China. Histology revealed infection by a microsporidian parasite within the cytoplasm of the epithelial cells of the hepatopancreas. Numerous discrete inclusions in the infected cells and presumably free parasite spores were also observed. By negative staining using electron microscopy, a typical morphology of spores was observed with a protuberant front of the anchoring disc. Infection was confined to the epithelial cells of the hepatopancreas, with no other organ implicated. By sequencing the PCR products using specific primers based on conserved regions of microsporidian small subunit (18S) ribosomal DNA , it was revealed that the parasite from HPND ponds had 99% sequence identity to that of Hepatospora eriocheir . Phylogentic analysis also placed the microsporidian in the same lineage as H. eriocheir . This study reported the first case of widespread infections of H. eriocheir associated with HPND found in the pond‐reared Chinese mitten crab, E. sinensis . The description of microsporidian in this important commercial host is fundamental for future consideration of factors affecting stock health and sustainability.

Comparison of MERIS, MODIS, SeaWiFS-derived particulate organic carbon, and in situ measurements in the South China Sea - S.B. Hu; W.X. Cao; G.F. Wang; Z.T. Xu; J. F. Lin; W.J. Zhao; Y.Z. Yang; W. Zhou; Z.H. Sun; L.J. Yao (International Journal of Remote Sensing, 2016)

Outbreak of NDM-1-producing Klebsiella pneumoniae ST76 and ST37 isolates in neonates - J. Zhu; L. Sun; B. Ding; Y. Yang; X. Xu; W. Liu; D. Zhu; F. Yang; H. Zhang; F. Hu (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Down-regulation of Arabidopsis DND1 orthologs in potato and tomato leads to broad-spectrum resistance to late blight and powdery mildew - Kaile Sun; Anne-Marie A. Wolters; Annelies E. H. M. Loonen; Robin P. Huibers; René van der Vlugt; Aska Goverse; Evert Jacobsen; Richard G. F. Visser; Yuling Bai (Transgenic Research, 2016)

The spatial‐temporal expression and functional divergence of bach homologs in zebrafish Danio rerio - Q. Luo; C. Wu; S. Sun; F. Lu; L. Xie; H. Zhao; X. Zhong; Q. Zhou (Journal of Fish Biology, 2016)
The spatial‐temporal expressions of bach1a , bach1b , bach2a and bach2b in early development of zebrafish Danio rerio embryos were examined in the present study by whole mount in situ hybridization. Transcripts of all genes were found at the one cell stage, suggesting that these four genes are maternally inherited. From the phylogenetic analyses, Bach1a and Bach1b from fishes form a well‐supported group with two sub‐groups. Bach2a and Bach2b, however, did not fall into one clade, suggesting that Bach2 proteins diverged faster or earlier than Bach1 proteins in fishes. The differentially regulated expression of the exocrine zymogen (such as the trypsin‐like gene, tryl ) of both paralogs of bach1 and bach2, respectively, showed that their functions are still active and already divergent, coinciding with subfunction partitioning.

Visual detection technique for efficient screening and isolation of Salmonella based on a novel enrichment assay using chromatography membrane - F. Tang; Y. Xiong; H. Zhang; K. Wu; Y. Xiang; J.-B. Shao; H.-W. Ai; Y.-P. Xiang; X.-L. Zheng; J.-R. Lv; H. Sun; L.-S. Bao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Simulation of Asymmetric Destabilization of Mine-void Rock Masses Using a Large 3D Physical Model - X. P. Lai; P. F. Shan; J. T. Cao; F. Cui; H. Sun (Rock Mechanics and Rock Engineering, 2016)

Epidemiology and characteristics of the dengue outbreak in Guangdong, Southern China, in 2014 - L. Huang; X. Luo; J. Shao; H. Yan; Y. Qiu; P. Ke; W. Zheng; B. Xu; W. Li; D. Sun; D. Cao; C. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Drought tolerance as a driver of tropical forest assembly: resolving spatial signatures for multiple processes - M. K. Bartlett; Y. Zhang; J. Yang; N. Kreidler; S.‐W. Sun; L. Lin; Y.‐H. Hu; K.‐F. Cao; L. Sack (Ecology, 2016)
Spatial patterns in trait variation reflect underlying community assembly processes, allowing us to test hypotheses about their trait and environmental drivers by identifying the strongest correlates of characteristic spatial patterns. For 43 evergreen tree species (>1 cm dbh) in a 20‐ha seasonal tropical rainforest plot in Xishuangbanna, China, we compared the ability of drought‐tolerance traits, other physiological traits, and commonly measured functional traits to predict the spatial patterns expected from the assembly processes of habitat associations, niche‐overlap‐based competition, and hierarchical competition. We distinguished the neighborhood‐scale (0–20 m) patterns expected from competition from larger‐scale habitat associations with a wavelet method. Species’ drought tolerance and habitat variables related to soil water supply were strong drivers of habitat associations, and drought tolerance showed a significant spatial signal for influencing competition. Overall, the traits most strongly associated with habitat, as quantified using multivariate models, were leaf density, leaf turgor loss point (π tlp ; also known as the leaf wilting point), and stem hydraulic conductivity ( r 2 range for the best fit models = 0.27–0.36). At neighborhood scales, species spatial associations were positively correlated with similarity in π tlp , consistent with predictions for hierarchical competition. Although the correlation between π tlp and interspecific spatial associations was weak ( r 2

TRPM7 Regulates Axonal Outgrowth and Maturation of Primary Hippocampal Neurons - Ekaterina Turlova; Christine Y. J. Bae; Marielle Deurloo; Wenliang Chen; Andrew Barszczyk; F. David Horgen; Andrea Fleig; Zhong-Ping Feng; Hong-Shuo Sun (Molecular Neurobiology, 2016)

Causes of WRF surface energy fluxes biases in a stratocumulus region - A. Jousse; A. Hall; F. Sun; J. Teixeira (Climate Dynamics, 2016)

Vertical stratification of moths across elevation and latitude - Louise A. Ashton; Akihiro Nakamura; Yves Basset; Chris J. Burwell; Min Cao; Rodney Eastwood; Erica Odell; Evandro Gama de Oliveira; Karen Hurley; Masatoshi Katabuchi; Sarah Maunsell; James McBroom; et al. (Journal of Biogeography, 2016)
Aim There is little consensus as to whether stratification of arthropods between canopy and understorey in tropical and subtropical forests is commonplace and if the magnitude of stratification changes across different elevations and latitudes. We investigated broad‐scale patterns of vertical stratification of moths collected from extensive cross‐continental fieldwork in a variety of forest types, climates, elevations, latitudes and areas with differing biogeographical history. Location Tropical and subtropical rain forest in eastern Australia; tropical, subtropical and subalpine forest in Yunnan Province, China; and tropical rain forest in Panama, Vietnam, Brunei and Papua New Guinea. Methods Night‐flying moths were trapped from the upper canopy and understorey. We generated a total of 64 data sets to quantify vertical stratification of moths in terms of their species richness, using coverage‐based rarefaction, and assemblage composition, using standardized hierarchical beta diversity. Based on the average temperature lapse rate, we incorporated latitudinal differences into elevation and generated ‘corrected’ elevation for each location, and analysed its relationships with the magnitude of stratification. Results We found consistent differences between canopy and understorey assemblages at almost all rain forest locations across corrected elevational gradients. The magnitude of vertical stratification in species richness did not change with increasing corrected elevation. In contrast, the difference in assemblage composition increased with increasing corrected elevation in the Northern Hemisphere, while the opposite, albeit weak, trend was found in the Southern Hemisphere. Main conclusions Clear vertical stratification was evident in moth assemblages regardless of elevation and latitude. However, the degree to which assemblages are stratified between canopy and understorey is not uniformly related to elevation and latitude. Inconsistencies in the magnitude of vertical stratification between the Northern and Southern Hemisphere, may reflect, on one hand, deep‐time biogeographical differences between the land masses studied and, on the other, place‐to‐place differences in resource availability underpinning the observed moth assemblages.

Post-diagnosis adiposity and survival among breast cancer patients: influence of breast cancer subtype - Xuezheng Sun; Hazel B. Nichols; Whitney Robinson; Mark E. Sherman; Andrew F. Olshan; Melissa A. Troester (Cancer Causes & Control, 2015)

Runoff characteristics and non-point source pollution analysis in the Taihu Lake Basin: a case study of the town of Xueyan, China - Q. D. Zhu; J. H. Sun; G. F. Hua; J. H. Wang; H. Wang (Environmental Science and Pollution Research, 2015)

Molecular epidemiology of carbapenemase-producing Escherichia coli and the prevalence of ST131 subclone H30 in Shanghai, China - F. Zhang; D. Zhu; L. Xie; X. Guo; Y. Ni; J. Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

H2O2 Exposure Affects Myotube Stiffness and Actin Filament Polymerization - Sing Wan Wong; Shan Sun; Michael Cho; Kenneth K. H. Lee; Arthur F. T. MAK (Annals of Biomedical Engineering, 2015)

Using fuzzy logic to generate conditional probabilities in Bayesian belief networks: a case study of ecological assessment - K. F.-R. Liu; J.-Y. Kuo; K. Yeh; C.-W. Chen; H.-H. Liang; Y.-H. Sun (International Journal of Environmental Science and Technology, 2015)

Identification of the trehalose-6-phosphate synthase gene family in winter wheat and expression analysis under conditions of freezing stress - D. W. XIE; X. N. WANG; L. S. FU; J. SUN; W. ZHENG; Z. F. LI (Journal of Genetics, 2015)

Genetic analysis for main length ratio associated with morphological traits in Japanese flounder Paralichthys olivaceus - Y. X. Liu; Z. H. Sun; Y. F. Wang; R. Q. Yang (Journal of Fish Biology, 2015)
The objective of this study was to estimate genetic parameters of main length ratios associated with morphological traits in Paralichthys olivaceus . At 180, 240 and 360 days of age, body length ( L 1 ), head length ( L 2 ), body depth ( L 3 ), caudal peduncle depth ( L 4 ) and caudal‐peduncle length ( L 5 ) were observed in 4757–5224 individuals from 52 full‐sib families. Based on these observed traits, the main length‐ratio traits including L 3 : L 1 , L 2 : L 1 , L 5 : L 1 and L 4 : L 3 were constructed. Three single‐trait animal models were used to examine the phenotypic variation of length‐ratio traits and were compared using the likelihood ratio test. As a result, the optimal model for all the analysed traits was determined as the model with the fixed, additive genetic and full‐sib family effects. Using the optimal model, animal model analysis for single trait showed that heritabilities were estimated to be low, ranging from 0·122 to 0·276. The estimates for all length‐ratio traits decreased while the days of age increased except for L 3 : L 1 . Multivariate animal model analysis indicated that within and among days of age, genetic correlations between length‐ratio traits were different in the direction and magnitude. Genetic parameter estimation of main length ratios would be helpful for genetic improvement of body shape in P. olivaceus .

Climatic variability, hydrologic anomaly, and methane emission can turn productive freshwater marshes into net carbon sources - Housen Chu; Johan F. Gottgens; Jiquan Chen; Ge Sun; Ankur R. Desai; Zutao Ouyang; Changliang Shao; Kevin Czajkowski (Global Change Biology, 2015)
Freshwater marshes are well‐known for their ecological functions in carbon sequestration, but complete carbon budgets that include both methane ( CH 4 ) and lateral carbon fluxes for these ecosystems are rarely available. To the best of our knowledge, this is the first full carbon balance for a freshwater marsh where vertical gaseous [carbon dioxide ( CO 2 ) and CH 4 ] and lateral hydrologic fluxes (dissolved and particulate organic carbon) have been simultaneously measured for multiple years (2011–2013). Carbon accumulation in the sediments suggested that the marsh was a long‐term carbon sink and accumulated ~96.9 ± 10.3 (±95% CI ) g C m −2 yr −1 during the last ~50 years. However, abnormal climate conditions in the last 3 years turned the marsh to a source of carbon (42.7 ± 23.4 g C m −2 yr −1 ). Gross ecosystem production and ecosystem respiration were the two largest fluxes in the annual carbon budget. Yet, these two fluxes compensated each other to a large extent and led to the marsh being a CO 2 sink in 2011 (−78.8 ± 33.6 g C m −2 yr −1 ), near CO 2 ‐neutral in 2012 (29.7 ± 37.2 g C m −2 yr −1 ), and a CO 2 source in 2013 (92.9 ± 28.0 g C m −2 yr −1 ). The CH 4 emission was consistently high with a three‐year average of 50.8 ± 1.0 g C m −2 yr −1 . Considerable hydrologic carbon flowed laterally both into and out of the marsh (108.3 ± 5.4 and 86.2 ± 10.5 g C m −2 yr −1 , respectively). In total, hydrologic carbon fluxes contributed ~23 ± 13 g C m −2 yr −1 to the three‐year carbon budget. Our findings highlight the importance of lateral hydrologic inflows/outflows in wetland carbon budgets, especially in those characterized by a flow‐through hydrologic regime. In addition, different carbon fluxes responded unequally to climate variability/anomalies and, thus, the total carbon budgets may vary drastically among years.

Studies on Different Iron Source Absorption by in Situ Ligated Intestinal Loops of Broilers - Y. F. Jia; M. M. Jiang; J. Sun; R. B. Shi; D. S. Liu (Biological Trace Element Research, 2015)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Establishment and characterization of an ovarian cell line from half‐smooth tongue sole Cynoglossus semilaevis - A. Sun; T. Z. Wang; N. Wang; X. F. Liu; Z. X. Sha; S. L. Chen (Journal of Fish Biology, 2015)
A new ovarian cell line, CSO , was established from half‐smooth tongue sole Cynoglossus semilaevis . Primary culture of CSO cells was initiated from digestion of ovarian tissues pieces by trypsin solution and cultured at 24° C in Dulbecco's modified Eagle's medium– F12 medium ( DMEM – F12 , 1:1) (pH 7·0), supplemented with 20% foetal bovine serum, basic fibroblast growth factor ( bFGF ), epidermal growth factor ( EGF ), insulin‐like growth factor‐I ( IGF ‐I) and human chorionic gonadotropin ( HCG ). The cultured CSO cells, fibroblastic in morphology, proliferated to 100% confluency 3 days later and had been subcultured to passage 80. Chromosome analyses indicated that the CSO cells exhibited chromosomal aneuploidy with a modal chromosome number of 42 that displayed the normal diploid karyotype of C. semilaevis [2 n = 42 t, fundamental number ( N F ) = 42]. Reverse transcription polymerase chain reaction revealed that CSO cells could express ovarian somatic cell functional genes p 450 armo , foxl2 and sox9a but not ovary germ cell marker gene vasa and male‐specific gene dmrt1 . Transfection experiment demonstrated that CSO cells transfected with pEGFP‐N3 plasmid could express green fluorescence protein ( GFP ) with higher transfection efficiency. The CSO cell line might serve as a valuable tool for studies on the mechanism of sex determination and oogenesis of ovary in flatfish.

AdeRS combination codes differentiate the response to efflux pump inhibitors in tigecycline-resistant isolates of extensively drug-resistant Acinetobacter baumannii - J.-R. Sun; C.-L. Perng; J.-C. Lin; Y.-S. Yang; M.-C. Chan; T.-Y. Chang; F.-M. Lin; T.-S. Chiueh (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Establishment of a novel triple-transgenic mouse: conditionally and liver-specifically expressing hepatitis C virus NS3/4A protease - H. Y. Lan; Y. Zhao; J. Yang; M. N. Sun; Y. F. Lei; M. Yao; X. J. Huang; J. M. Zhang; Z. K. Xu; X. Lü; W. Yin (Molecular Biology Reports, 2014)

The conservation of Rhododendrons is of greater urgency than has been previously acknowledged in China - Yongpeng Ma; Jens Nielsen; David F. Chamberlain; Xiaoya Li; Weibang Sun (Biodiversity and Conservation, 2014)

Evaluation of tebuconazole for the management of Fusarium head blight in China - H.-Y. Sun; Y.-F Zhu; Y.-Y. Liu; Y.-Y. Deng; W. Li; A.-X. Zhang; H.-G. Chen (Australasian Plant Pathology, 2014)

Effect of Manure Treatment on Ammonia Emission during Storage under Ambient Environment - F. Sun; J. H. Harrison; P. M. Ndegwa; K. Johnson (Water, Air, & Soil Pollution, 2014)

Risk factors for bacterial vaginosis: results from a cross-sectional study having a sample of 53,652 women - X.-D. Li; C.-C. Wang; X.-J. Zhang; G.-P. Gao; F. Tong; X. Li; S. Hou; L. Sun; Y.-H. Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Meta-discoveries from a synthesis of satellite-based land-cover mapping research - Le Yu; Lu Liang; Jie Wang; Yuanyuan Zhao; Qu Cheng; Luanyun Hu; Shuang Liu; Liang Yu; Xiaoyi Wang; Peng Zhu; Xueyan Li; Yue Xu; et al. (International Journal of Remote Sensing, 2014)

Effect of Manure Treatment on Ammonia and Greenhouse Gases Emissions Following Surface Application - F. Sun; J. H. Harrison; P. M. Ndegwa; K. Johnson (Water, Air, & Soil Pollution, 2014)

Functions of the CCCH type zinc finger protein OsGZF1 in regulation of the seed storage protein GluB-1 from rice - Yi Chen; Aijun Sun; Mei Wang; Zhen Zhu; Pieter B. F. Ouwerkerk (Plant Molecular Biology, 2014)

Stability analysis of a large landslide in hydropower engineering - Y. Zhang; J. F. Shao; W. Y. Xu; H. K. Sun (Natural Hazards, 2014)

CpG methylation of dmrt1 and cyp19a promoters in relation to their sexual dimorphic expression in the Japanese flounder Paralichthys olivaceus - A. Y. Wen; F. You; P. Sun; J. Li; D. D. Xu; Z. H. Wu; D. Y. Ma; P. J. Zhang (Journal of Fish Biology, 2014)
To better understand the effects of DNA methylation on the expression patterns of dmrt1 (Doublesex and Mab‐3‐related transcription factor 1) and cyp19a (Cytochrome P450 19a) in the Japanese flounder Paralichthys olivaceus , quantitative expressions, cellular distributions and cytosine‐p‐guanine (CpG) methylation patterns of these two genes in the gonads were analysed. The results showed that P. olivaceus dmrt1 expression was 70 times higher in the testis than in the ovary ( P mRNA was detected clearly in spermatocytes and Sertoli cells of the testis, but weakly in the ovary. Paralichthys olivaceus cyp19a expression was 40 times higher in the ovary than in the testis ( P mRNA was detected clearly in follicular cells of the ovary, but weakly in spermatocytes of the testis. The dmrt1 promoter CpGs were not methylated in the testis, whereas 57·69% were methylated in the ovary. For the cyp19a promoter CpGs , 97·5% were methylated in the testis and 73·33% were methylated in the ovary. These findings demonstrate that P. olivaceus dmrt1 and cyp19a are sex‐related genes with sexual dimorphic expression, CpG methylation levels of the two genes are consistent with their expression quantities, and this epigenetic modification can influence the differential expression of genes in the gonads of P. olivaceus .

Clinical and epidemiological survey and analysis of the first case of human infection with avian influenza A(H7N9) virus in Hangzhou, China - L. Xie; H. Ding; Q.-J. Kao; X.-H. Yang; Y.-Y. Wen; H.-K. Lv; Z.-P. Chen; E.-F. Chen; Z. Sun; J.-C. Pan; X.-Y. Pu; J. Li; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Effects of allelic variations in glutenin and waxy proteins on dough alveogram properties and Chinese white salt noodle qualities - Z. Deng; S. Hu; F. Chen; J. Chen; X. Zhang; J. Chen; C. Sun; Y. Zhang; J. Tian (Cereal Research Communications, 2013)

Erratum to: Short and long access to cocaine self-administration activates tyrosine phosphatase STEP and attenuates GluN expression but differentially regulates GluA expression in the prefrontal cortex - Wei-Lun Sun; Agnieszka Zelek-Molik; Jacqueline F. McGinty (Psychopharmacology, 2013)

Short and long access to cocaine self-administration activates tyrosine phosphatase STEP and attenuates GluN expression but differentially regulates GluA expression in the prefrontal cortex - Wei-Lun Sun; Agnieszka Zelek-Molik; Jacqueline F. McGinty (Psychopharmacology, 2013)

High Variation in Single Nucleotide Polymorphisms (SNPs) and Insertions/Deletions (Indels) in the Highly Invasive Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) Middle East-Asia Minor 1 (MEAM1) - Z C Lü; H B Sun; F H Wan; J Y Guo; G F Zhang (Neotropical Entomology, 2013)

Changes of public environmental awareness in response to the Taihu blue-green algae bloom incident in China - L. Xu; J. Shen; D. Marinova; X. Guo; F. Sun; F. Zhu (Environment, Development and Sustainability, 2013)

Petrographic and structural analysis of the Precambrian rocks in the Zalbi Sector, northwest Léré, Chad - F. Sun; L. Tekoum; J. C. Doumnang; R. Tchameni; A. A. Ganwa (Australian Journal of Earth Sciences, 2013)

QTL analysis of the spring wheat “Chapio” identifies stable stripe rust resistance despite inter-continental genotype × environment interactions - E.-N. Yang; G. M. Rosewarne; S. A. Herrera-Foessel; J. Huerta-Espino; Z.-X. Tang; C.-F. Sun; Z.-L. Ren; R. P. Singh (Theoretical and Applied Genetics, 2013)

Impacts of increased variability in precipitation and air temperature on net primary productivity of the Tibetan Plateau: a modeling analysis - Jian-Sheng Ye; James F. Reynolds; Guo-Jun Sun; Feng-Min Li (Climatic Change, 2013)

Anagenetic speciation in Ullung Island, Korea: genetic diversity and structure in the island endemic species, Acer takesimense (Sapindaceae) - Koji Takayama; Byung-Yun Sun; Tod F. Stuessy (Journal of Plant Research, 2013)

Identification of a novel bluetongue virus 1-specific B-cell epitope using a monoclonal antibody against the VP2 protein - P. Wei; E. C. Sun; N. H. Liu; T. Yang; Q. Y. Xu; J. Zhao; Y. L. Qin; Y. F. Feng; J. P. Li; W. S. Wang; C. Y. Zhang; D. L. Wu (Archives of Virology, 2013)

Evaluation of a reliable and cost-effective method of DNA isolation for mouse genotyping - Justin R. Sysol; Carrie Kempf; Michelle N. Helton; Yangbasai Dong; Daocheng Zhu; Haiying Sun; Joe G. N. Garcia; Roberto F. Machado; Jiwang Chen (Biotechnology Letters, 2013)

Phage mutations in response to CRISPR diversification in a bacterial population - Christine L. Sun; Rodolphe Barrangou; Brian C. Thomas; Philippe Horvath; Christophe Fremaux; Jillian F. Banfield (Environmental Microbiology, 2013)
Summary Interactions between bacteria and their coexisting phage populations impact evolution and can strongly influence biogeochemical processes in natural ecosystems. Periodically, mutation or migration results in exposure of a host to a phage to which it has no immunity; alternatively, a phage may be exposed to a host it cannot infect. To explore the processes by which coexisting, co‐evolving hosts and phage populations establish, we cultured S treptococcus thermophilus DGCC 7710 with phage 2972 and tracked CRISPR (clustered regularly interspaced short palindromic repeats) diversification and host–phage co‐evolution in a population derived from a colony that acquired initial CRISPR ‐encoded immunity. After 1 week of co‐culturing, the coexisting host–phage populations were metagenomically characterized using 454 FLX T itanium sequencing. The evolved genomes were compared with reference genomes to identify newly incorporated spacers in S . thermophilus DGCC 7710 and recently acquired single‐nucleotide polymorphisms ( SNPs ) in phage 2972. Following phage exposure, acquisition of immune elements (spacers) led to a genetically diverse population with multiple subdominant strain lineages. Phage mutations that circumvented three early immunization events were localized in the proto‐spacer adjacent motif ( PAM ) or near the PAM end of the proto‐spacer, suggesting a strong selective advantage for the phage that mutated in this region. The sequential fixation or near fixation of these single mutations indicates selection events so severe that single phage genotypes ultimately gave rise to all surviving lineages and potentially carried traits unrelated to immunity to fixation.

A population-based analysis of the effect of marital status on overall and cancer-specific mortality in patients with squamous cell carcinoma of the penis - Rodolphe Thuret; Maxine Sun; Lars Budaus; Firas Abdollah; Daniel Liberman; Shahrokh F. Shariat; François Iborra; Jacques Guiter; Jean-Jacques Patard; Paul Perrotte; Pierre I. Karakiewicz (Cancer Causes & Control, 2013)

A short account on the Eocene fish fauna from Huadian (Jilin Province, China) - Jean Gaudant; Stephan F. K. Schaal; Sun Wei (Palaeobiodiversity and Palaeoenvironments, 2012)

Meat Quality Evaluation by Hyperspectral Imaging Technique: An Overview - Gamal Elmasry; Douglas F. Barbin; Da-Wen Sun; Paul Allen (Critical Reviews in Food Science and Nutrition, 2012)

Characterization of a novel Klebsiella pneumoniae sequence type 476 carrying both bla KPC-2 and bla IMP-4 - Y. Wang; W. Cao; X. Zhu; Z. Chen; L. Li; B. Zhang; B. Wang; L. Tian; F. Wang; C. Liu; Z. Sun (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Uncertainty Estimate of Surface Irradiances Computed with MODIS-, CALIPSO-, and CloudSat-Derived Cloud and Aerosol Properties - Seiji Kato; Norman G. Loeb; David A. Rutan; Fred G. Rose; Sunny Sun-Mack; Walter F. Miller; Yan Chen (Surveys in Geophysics, 2012)

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

A preliminary study on the molecular evolution of the two routes of intrauterine transmission of HBV - H. Sun; X. Tang; B. Wang; J. Zhang; H. Cheng; H. Su; F. Li; K. Men; S. Wang; L. Zhao; J. Xu; X. Yu; et al. (Archives of Virology, 2012)

Linkage analysis of plasma dopamine β-hydroxylase activity in families of patients with schizophrenia - Joseph F. Cubells; Xiangqing Sun; Wenbiao Li; Robert W. Bonsall; John A. McGrath; Dimitri Avramopoulos; Virginia K. Lasseter; Paula S. Wolyniec; Yi-Lang Tang; Kristina Mercer; Ann E. Pulver; Robert C. Elston (Human Genetics, 2011)

Isolation, sequence analysis, and characterization of androgen receptor in Southern catfish, Silurus meridionalis - B. F. Huang; Y. L. Sun; F. R. Wu; Z. H. Liu; Z. J. Wang; L. F. Luo; Y. G. Zhang; D. S. Wang (Fish Physiology and Biochemistry, 2011)

Influence of rocky slope gradient on root anchorage of Vitex negundo L. - F. Long; H.-L. Sun; S.-C. Li (Plant Biosystems, 2011)

The effect of marital status on stage and survival of prostate cancer patients treated with radical prostatectomy: a population-based study - Firas Abdollah; Maxine Sun; Rodolphe Thuret; Al’a Abdo; Monica Morgan; Claudio Jeldres; Shahrokh F. Shariat; Paul Perrotte; Francesco Montorsi; Pierre I. Karakiewicz (Cancer Causes & Control, 2011)

Probabilistic acute dietary exposure assessment of the Chinese population to cypermethrin residues - J.-F. Sun; P. Liu; C.-Y. Li; J.-X. Li; C.-N. Wang; J. Min; D. Hu; Y.-N. Wu (Food Additives & Contaminants: Part A, 2011)

Brominated flame retardants in Canadian chicken egg yolks - D.F.K. Rawn; A. Sadler; S.C. Quade; W.-F. Sun; B.P.-Y. Lau; I. Kosarac; S. Hayward; J.J. Ryan (Food Additives & Contaminants: Part A, 2011)

Calculation of the dietary exposure of Chinese consumers to acephate residues using deterministic and probabilistic approaches - P. Liu; C.-Y. Li; C.-N. Wang; J.-F. Sun; J. Min; D. Hu; Y.-N. Wu (Food Additives & Contaminants: Part A, 2011)

Inheritance of stripe rust resistance to predominant Chinese races in six spring wheat cultivars from the pacific Northwest of the United States - Y. Gao; Q. Sun; R. Wang; J. Feng; F. Lin; N. Cui; X. Chen; S. Xu; Y. Bai; X. Xu (Cereal Research Communications, 2011)

Distribution of denitrifying bacterial communities in the stratified water column and sediment–water interface in two freshwater lakes and the Baltic Sea - Ok-Sun Kim; Johannes F. Imhoff; Karl-Paul Witzel; Pilar Junier (Aquatic Ecology, 2011)

Non-Darcy Free Convection of Power-Law Fluids Over a Two-Dimensional Body Embedded in a Porous Medium - M. F. El-Amin; S. Sun; M. A. El-Ameen; Y. A. Jaha; Rama Subba Reddy Gorla (Transport in Porous Media, 2011)

Geographic distribution of phylogenetically-distinct legume pod borer, Maruca vitrata (Lepidoptera: Pyraloidea: Crambidae) - Venu M. Margam; Brad S. Coates; Malick N. Ba; Weilin Sun; Clementine L. Binso-Dabire; Ibrahim Baoua; Mohammad F. Ishiyaku; John T. Shukle; Richard L. Hellmich; Fernando G. Covas; Srinivasan Ramasamy; Joel Armstrong; et al. (Molecular Biology Reports, 2011)

Comparing the Community Composition of European and Eastern Chinese Waterbirds and the Influence of Human Factors on the China Waterbird Community - Willem F. de Boer; Lei Cao; Mark Barter; Xin Wang; Mengmeng Sun; Herman van Oeveren; Jan de Leeuw; Jeb Barzen; Herbert H. T. Prins (Ambio, 2011)

Long-term dietary exposure to lead of the population of Jiangsu Province, China - J.-F. Sun; C.-N. Wang; Y.-N. Wu; B.-J. Yuan; Z.-H. Tian; X.-Y. Song; C.-Y. Li; P. Liu (Food Additives & Contaminants: Part A, 2011)

An Impact Assessment Method of Dam/Sluice on Instream Ecosystem and its Application to the Bengbu Sluice of China - C. S. Zhao; C. L. Sun; J. Xia; X. P. Hao; G. F. Li; K. Rebensburg; C. M. Liu (Water Resources Management, 2010)

Dual inexact fuzzy chance-constrained programming for planning waste management systems - M. F. Cao; G. H. Huang; Y. Sun; Y. Xu; Y. Yao (Stochastic Environmental Research and Risk Assessment, 2010)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

Relationship of genetic distance and hybrid performance in hybrids derived from a new photoperiod-thermo sensitive male sterile wheat line 337S - Xiaodong Chen; Dongfa Sun; D. F. Rong; Genlou Sun; Junhua Peng (Euphytica, 2010)

Population genetic structure and larval dispersal potential of spottedtail goby Synechogobius ommaturus in the north‐west Pacific - N. Song; X. M. Zhang; X. F. Sun; T. Yanagimoto; T. X. Gao (Journal of Fish Biology, 2010)
Larval dispersal may have an important effect on genetic structure of benthic fishes. To examine the population genetic structure of spottedtail goby Synechogobius ommaturus , a 478 base pair (bp) fragment of the hypervariable portion of the mtDNA control region was sequenced and used to interpret life‐history characteristics and larval dispersal strategy. Individuals ( n = 186) from 10 locations on the coasts of China and Korea were analysed and 44 haplotypes were obtained. The levels of haplotype and nucleotide diversity were higher in East China Sea populations than in other populations. Both the phylogenetic tree and the minimum spanning tree showed that no significant genealogical structures corresponding to sampling locations existed. AMOVA and pair‐wise F ST revealed significant genetic differentiation between populations from Korea and China. A significant isolation by distance pattern was observed in this species ( r = 0·53, P S. ommaturus to have experienced a recent population expansion. These results suggest that the Pleistocene ice ages had a major effect on the phylogeographic pattern of S. ommaturus , that larvae might avoid offshore dispersal and that dispersal of larvae may maintain a migration–drift equilibrium.

In silico characterization of the functional and structural modules of the hemagglutinin protein from the swine-origin influenza virus A (H1N1)-2009 - YePing Sun; Yi Shi; Wei Zhang; Qing Li; Di Liu; Christopher Vavricka; JingHua Yan; George F. Gao (Science China Life Sciences, 2010)

Matched pairs of human prostate stromal cells display differential tropic effects on LNCaP prostate cancer cells - Xiaojuan Sun; Hui He; Zhihui Xie; Weiping Qian; Haiyen E. Zhau; Leland W. K. Chung; Fray F. Marshall; Ruoxiang Wang (In Vitro Cellular & Developmental Biology - Animal, 2010)

Influence of size and seasonal factors on the growth of the deep-sea coral Flabellum alabastrum in mesocosm - J.-F. Hamel; Z. Sun; A. Mercier (Coral Reefs, 2010)

Mapping quantitative trait loci for quality factors in an inter-class cross of US and Chinese wheat - Xiaochun Sun; Felix Marza; Hongxiang Ma; Brett F. Carver; Guihua Bai (Theoretical and Applied Genetics, 2010)

It is not just AIV: From avian to swine-origin influenza virus - George F. Gao; YePing Sun (Science China Life Sciences, 2010)

Study on blood cultures and bacteria counts in the blood of paratyphoid fever A patients - S. K. Wang; C. J. Chu; P. S. Sun; D. S. Shan; F. L. Kong; H. Y. Liu; Q. Wu; R. S. Yang; Y. B. Yao (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

End-Permian to mid-Triassic termination of the accretionary processes of the southern Altaids: implications for the geodynamic evolution, Phanerozoic continental growth, and metallogeny of Central Asia - W. J. Xiao; B. F. Windley; B. C. Huang; C. M. Han; C. Yuan; H. L. Chen; M. Sun; S. Sun; J. L. Li (International Journal of Earth Sciences, 2009)

Evidence that TGFA influences risk to cleft lip with/without cleft palate through unconventional genetic mechanisms - Jae Woong Sull; Kung-Yee Liang; Jacqueline B. Hetmanski; Tao Wu; Margaret Daniele Fallin; Roxann G. Ingersoll; Ji Wan Park; Yah-Huei Wu-Chou; Philip K. Chen; Samuel S. Chong; Felicia Cheah; Vincent Yeow; et al. (Human Genetics, 2009)

Planulation of deep-sea octocorals in the NW Atlantic - Z. Sun; J.-F. Hamel; A. Mercier (Coral Reefs, 2009)

The occurrence of the feline “Candidatus Mycoplasma haemominutum” in dog in China confirmed by sequence-based analysis of ribosomal DNA - Q. J. Zhuang; H. J. Zhang; R. Q. Lin; M. F. Sun; X. J. Liang; X. W. Qin; W. J. Pu; X. Q. Zhu (Tropical Animal Health and Production, 2009)

Two late Mesozoic volcanic events in Fujian Province: constraints on the tectonic evolution of southeastern China - L.‐M. Li; M. Sun; G.‐F. Xing; G.‐C. Zhao; M.‐F. Zhou; J. Wong; R. Chen (International Geology Review, 2009)

The carp M1 muscle‐specific creatine kinase subisoform is adaptive to the synchronized changes in body temperature and intracellular pH that occur in the common carp Cyprinus carpio - C. L. Wu; C. W. Liu; H. W. Sun; H. C. Chang; C. J. Huang; C. F. Hui; J. L. Wu (Journal of Fish Biology, 2008)
The three previously cloned Cyprinus carpio muscle‐specific subisoforms of creatine kinase (CK, EC 2.7.3.2) designated M1‐, M2‐ and M3‐CK were examined. At temperatures 7·7, specific activities of M1‐CK were three to eight‐fold higher than specific activities of M3‐ and rabbit (R) M‐CK. At pH 8·0, M1‐CK exhibited its highest specific activity at 15° C. Michaelis constants of PCr ( ) and ADP ( ) of M1‐CK were relatively stable at pH between 7·1–8·0 and 25–5° C. Its calculated activation energy of catalysis ( E a ) at pH 8·0 was lower than at pH 7·1. Circular dichroism spectroscopy results showed that changes in secondary structures in M1‐CK at the pH and temperatures studied were much less than in the cases of RM‐ and M3‐CK. The M1‐CK enzyme seemed to have evolved to adapt to the synchronized changes in body temperature and intracellular pH of C. carpio .

Genetic analysis of photoperiod sensitivity in a tropical by temperate maize recombinant inbred population using molecular markers - C. L. Wang; F. F. Cheng; Z. H. Sun; J. H. Tang; L. C. Wu; L. X. Ku; Y. H. Chen (Theoretical and Applied Genetics, 2008)

Critical Environmental Flows to Support Integrated Ecological Objectives for the Yellow River Estuary, China - T. Sun; Z. F. Yang; B. S. Cui (Water Resources Management, 2008)

Immunological mechanisms in glaucoma - F. Grus; D. Sun (Seminars in Immunopathology, 2008)

Associated changes in physiological parameters and spectral reflectance indices in olive ( Olea europaea L.) leaves in response to different levels of water stress - P. Sun; A. Grignetti; S. Liu; R. Casacchia; R. Salvatori; F. Pietrini; F. Loreto; M. Centritto (International Journal of Remote Sensing, 2008)

Effect of HCH contamination of diet on the growth performance and immune and antioxidant ability in growing/finishing pigs - F. Wang; Z. R. Xu; J. H. Sun (Veterinary Research Communications, 2008)

Community composition of ammonia-oxidizing bacteria in the rhizosphere of intercropped wheat (Triticum aestivum L.), maize (Zea mays L.), and faba bean (Vicia faba L.) - Y. N. Song; P. Marschner; L. Li; X. G. Bao; J. H. Sun; F. S. Zhang (Biology and Fertility of Soils, 2007)

Floral traits and isolation of three sympatric Aquilegia species in the Qinling Mountains, China - L.-L. Tang; Q. Yu; J.-F. Sun; S.-Q. Huang (Plant Systematics and Evolution, 2007)

Generation of a velogenic Newcastle disease virus from cDNA and expression of the green fluorescent protein - Y. L. Liu; S. L. Hu; Y. M. Zhang; S. J. Sun; A. Romer-Oberdorfer; J. Veits; Y. T. Wu; H. Q. Wan; X. F. Liu (Archives of Virology, 2007)

Allelic variation of polyphenol oxidase (PPO) genes located on chromosomes 2A and 2D and development of functional markers for the PPO genes in common wheat - X. Y. He; Z. H. He; L. P. Zhang; D. J. Sun; C. F. Morris; E. P. Fuerst; X. C. Xia (Theoretical and Applied Genetics, 2007)

Local problem-based a posteriori error estimators for discontinuous Galerkin approximations of reactive transport - Shuyu Sun; Mary F. Wheeler (Computational Geosciences, 2007)

Effect of intercropping on crop yield and chemical and microbiological properties in rhizosphere of wheat (Triticum aestivum L.), maize (Zea mays L.), and faba bean (Vicia faba L.) - Y. N. Song; F. S. Zhang; P. Marschner; F. L. Fan; H. M. Gao; X. G. Bao; J. H. Sun; L. Li (Biology and Fertility of Soils, 2007)

Developmental regulation of SSeCKS expression in rat brain - L. Chen; J. Qin; C. Cheng; H. Liu; J. Qian; L. Sun; F. Xiao; S. Shi; S. Niu; A. Shen (Journal of Molecular Neuroscience, 2007)

Src suppressed C kinase substrate regulates the lipopolysaccharide-induced TNF-α biosynthesis in rat astrocytes - L. -l. Sun; C. Cheng; H. -o. Liu; C. -c. Shen; F. Xiao; J. Qin; J. -l. Yang; A. -g. Shen (Journal of Molecular Neuroscience, 2007)

Gene expression profiles analysis of the growing rat liver in response to different zinc status by cDNA microarray analysis - J. Y. Sun; J. F. Wang; N. T. Zl; M. Y. Jing; X. Y. Weng (Biological Trace Element Research, 2007)

Gene expression profiles analysis of the growing rat liver in response to different zinc status by cDNA microarray analysis - J. Y. Sun; J. F. Wang; N. T. Zl; M. Y. Jing; X. Y. Weng (Biological Trace Element Research, 2007)

Long terminal repeats are not the sole determinants of virulence for equine infectious anemia virus - Y.-B. Tu; T. Zhou; X.-F. Yuan; H.-J. Qiu; F. Xue; C.-Q. Sun; L. Wang; D.-L. Wu; J.-M. Peng; X.-G. Kong; G.-Z. Tong (Archives of Virology, 2007)

Response to Host Volatiles by Native and Introduced Populations of Dendroctonus valens (Coleoptera: Curculionidae, Scolytinae) in North America and China - N. Erbilgin; S. R. Mori; J. H. Sun; J. D. Stein; D. R. Owen; L. D. Merrill; R. Campos Bolaños; K. F. Raffa; T. Méndez Montiel; D. L. Wood; N. E. Gillette (Journal of Chemical Ecology, 2006)

Delimitation of Amaranthus cruentus L. and Amaranthus caudatus L. using micromorphology and AFLP analysis: an application in germplasm identification - M. Costea; D. M. Brenner; F. J. Tardif; Y. F. Tan; M. Sun (Genetic Resources and Crop Evolution, 2006)

Delimitation of Amaranthus cruentus L. and Amaranthus caudatus L. using micromorphology and AFLP analysis: an application in germplasm identification - M. Costea; D. M. Brenner; F. J. Tardif; Y. F. Tan; M. Sun (Genetic Resources and Crop Evolution, 2006)

Geochemical evidence for the variation of historical seabird population on Dongdao Island of the South China Sea - X. D. Liu; S. P. Zhao; L. G. Sun; H. H. Luo; X. B. Yin; Z. Q. Xie; Y. H. Wang; K. X. Liu; X. H. Wu; X. F. Ding; D. P. Fu (Journal of Paleolimnology, 2006)

Inhibition of urease by bismuth(III): Implications for the mechanism of action of bismuth drugs - Li Zhang; Scott B. Mulrooney; Andy F. K. Leung; Yibo Zeng; Ben B. C. Ko; Robert P. Hausinger; Hongzhe Sun (BioMetals, 2006)

Fertility alteration in the photo-thermo-sensitive male sterile line BS20 of wheat (Triticum aestivum L.) - Y. F. Li; C. P. Zhao; F. T. Zhang; H. Sun; D. F. Sun (Euphytica, 2006)

Analysis of MS2Bnap genomic DNA homologous to MS2 gene from Arabidopsis thaliana in two dominant digenic male sterile accessions of oilseed rape (Brassica napus L.) - S. W. Hu; Y. F. Fan; H. X. Zhao; X. L. Guo; C. Y. Yu; G. L. Sun; C. H. Dong; S. Y. Liu; H. Z. Wang (Theoretical and Applied Genetics, 2006)

Effects of Tween-80 on Bioremediation of Soil Contaminated with Resin and Asphalt - Z. Niu; S. Guo; F. Li; T. Sun (Bulletin of Environmental Contamination and Toxicology, 2006)

The TRAIL apoptotic pathway mediates proteasome inhibitor induced apoptosis in primary chronic lymphocytic leukemia cells - Albert F. Kabore; Jinmie Sun; Xiaojie Hu; Kristin McCrea; James B. Johnston; Spencer B. Gibson (Apoptosis, 2006)

Anagenetic evolution in island plants - Tod F. Stuessy; Gerhard Jakubowsky; Roberto Salguero Gómez; Martin Pfosser; Philipp M. Schlüter; Tomas Fer; Byung‐Yun Sun; Hidetoshi Kato (Journal of Biogeography, 2006)
Aim Plants in islands have often evolved through adaptive radiation, providing the classical model of evolution of closely related species each with strikingly different morphological and ecological features and with low levels of genetic divergence. We emphasize the importance of an alternative (anagenetic) model of evolution, whereby a single island endemic evolves from a progenitor and slowly builds up genetic variation through time. Location Continental and oceanic islands. Methods We surveyed 2640 endemic angiosperm species in 13 island systems of the world, both oceanic and continental, for anagenetic and cladogenetic patterns of speciation. Genetic data were evaluated from a progenitor and derivative species pair in Ullung Island, Korea, and Japan. Results We show that the anagenetic model of evolution is much more important in oceanic islands than previously believed, accounting for levels of endemic specific diversity from 7% in the Hawaiian Islands to 88% in Ullung Island, Korea, with a mean for all islands of 25%. Examination of an anagenetically derived endemic species in Ullung Island reveals genetic (amplified fragment length polymorphism) variation equal or nearly equal to that of its continental progenitor. Main conclusions We hypothesize that, during anagenetic speciation, initial founder populations proliferate, and then accumulate genetic variation slowly through time by mutation and recombination in a relatively uniform environment, with drift and/or selection yielding genetic and morphological divergence sufficient for the recognition of new species. Low‐elevation islands with low habitat heterogeneity are highly correlated with high levels of anagenetic evolution, allowing prediction of levels of the two models of evolution from these data alone. Both anagenetic and adaptive radiation models of speciation are needed to explain the observed levels of specific and genetic diversity in oceanic islands.

Effects of Tween-80 on Bioremediation of Soil Contaminated with Resin and Asphalt - Z. Niu; S. Guo; F. Li; T. Sun (Bulletin of Environmental Contamination and Toxicology, 2006)

Two recessive genes controlling thermophotoperiod-sensitive male sterility in wheat - R.X. Guo; D. F. Sun; Z. B. Tan; D. F. Rong; C. D. Li (Theoretical and Applied Genetics, 2006)

Root distribution and interactions between intercropped species - Long Li; Jianhao Sun; Fusuo Zhang; Tianwen Guo; Xingguo Bao; F. Andrew Smith; Sally E. Smith (Oecologia, 2006)

Verapamil modulates LPS-induced cytokine production via inhibition of NF-kappa B activation in the liver - G. Li; X. P. Qi; X. Y. Wu; F. K. Liu; Z. Xu; C. Chen; X. D. Yang; Z. Sun; J. S. Li (Inflammation Research, 2006)

Combination of temporal gravity variations resulting from superconducting gravimeter (SG) recordings, GRACE satellite observations and global hydrology models - J. Neumeyer; F. Barthelmes; O. Dierks; F. Flechtner; M. Harnisch; G. Harnisch; J. Hinderer; Y. Imanishi; C. Kroner; B. Meurers; S. Petrovic; Ch. Reigber; et al. (Journal of Geodesy, 2006)

Evolution of Dystaenia takesimana (Apiaceae), endemic to Ullung Island, Korea - M. Pfosser; G. Jakubowsky; P. M. Schlüter; T. Fer; H. Kato; T. F. Stuessy; B.-Y. Sun (Plant Systematics and Evolution, 2005)

Leaching Behavior of Copper (II) in a Soil Column Experiment - J. Xu; X. Han; S. Sun; F. Meng; S. Dai (Bulletin of Environmental Contamination and Toxicology, 2005)

Diversity and selection in sorghum: simultaneous analyses using simple sequence repeats - A. M. Casa; S. E. Mitchell; M. T. Hamblin; H. Sun; J. E. Bowers; A. H. Paterson; C. F. Aquadro; S. Kresovich (Theoretical and Applied Genetics, 2005)

An autosomal genomic scan for loci linked to type 2 diabetes in northern Han Chinese - J. Y. Zhao; M. M. Xiong; W. Huang; H. Wang; J. Zuo; G. D. Wu; Z. Chen; B. Q. Qiang; M. L. Zhang; J. L. Chen; W. Ding; W. T. Yuan; et al. (Journal of Molecular Medicine, 2005)

Air temperature retrieval from remote sensing data based on thermodynamics - Y.-J. Sun; J.-F. Wang; R.-H. Zhang; R. R. Gillies; Y. Xue; Y.-C. Bo (Theoretical and Applied Climatology, 2005)

Rapid non-genomic inhibitory effects of glucocorticoids on human neutrophil degranulation - L. Liu; Y. X. Wang; J. Zhou; F. Long; H. W. Sun; Y. Liu; Y. Z. Chen; C. L. Jiang (Inflammation Research, 2005)

A Device to Study the Initiation and Propagation of Calcium Transients in Cultured Neurons After Mechanical Stretch - Theresa A. Lusardi; Jeff Rangan; David Sun; Douglas H. Smith; David F. Meaney (Annals of Biomedical Engineering, 2004)

A study of gravity variations caused by polar motion using superconducting gravimeter data from the GGP network - J.-Q. Xu; H.-P. Sun; X.-F. Yang (Journal of Geodesy, 2004)

Metabolism and Disposition of the HIV-1 Protease Inhibitor Lopinavir (ABT-378) Given in Combination with Ritonavir in Rats, Dogs, and Humans - Gondi N. Kumar; Venkata K. Jayanti; Marianne K. Johnson; John Uchic; Samuel Thomas; Ronald D. Lee; Brian A. Grabowski; Hing L. Sham; Dale J. Kempf; Jon F. Denissen; Kennan C. Marsh; Eugene Sun; et al. (Pharmaceutical Research, 2004)

Residues of Hexachlorocyclohexane Isomers and Their Distribution Characteristics in Soils in the Tianjin Area, China - Z. M. Gong; F. L. Xu; R. Dawson; J. Cao; W. X. Liu; B. G. Li; W. R. Shen; W. J. Zhang; B. P. Qin; R. Sun; S. Tao (Archives of Environmental Contamination and Toxicology, 2004)

Inhibition of Angiogenesis by Aβ Peptides - Daniel Paris; Kirk Townsend; Amita Quadros; James Humphrey; Jiazhi Sun; Steven Brem; Marguerite Wotoczek-Obadia; Anthony DelleDonne; Nikunj Patel; Demian F. Obregon; Robert Crescentini; Laila Abdullah; et al. (Angiogenesis, 2004)

Applications of combined DNA microarray and chromosome sorting technologies - S. M. Gribble; H. Fiegler; D. C. Burford; E. Prigmore; F. Yang; P. Carr; B. L. Ng; T. Sun; E. S. Kamberov; V. L. Makarov; J. P. Langmore; N. P. Carter (Chromosome Research, 2004)

The Siva-1 putative amphipathic helical region (SAH) is sufficient to bind to BCL-XL and sensitize cells to UV radiation induced apoptosis - F. Chu; A. Borthakur; X. Sun; J. Barkinge; R. Gudi; S. Hawkins; K. V. S. Prasad (Apoptosis, 2004)

Bacterial roles in the formation of high‐molecular‐weight dissolved organic matter inestuarine and coastal waters: Evidence from lipids and the compound‐specificisotopic ratios - Li Zou; Xu-Chen Wang; Julie Callahan; Randolph A. Culp; Robert F. Chen; Mark A. Altabet; Ming-Yi Sun (Limnology and Oceanography, 2004)
High‐molecular‐weight dissolved organic matter (HMW‐DOM, > 1,000 Daltons) is actively involved in the global biogeochemical cycling of many elements, but its carbon sources and detailed formation pathways are still not well understood. In this study, we measured bulk stable carbon and nitrogen isotopic ratios, lipid composition, and compound‐specific carbon isotopic ratios of HMW‐DOM samples collected from four U.S. estuaries (Boston Harbor/Massachusetts Bay, Delaware/Chesapeake Bay, San Diego Bay, and San Francisco Bay). Analytical results show (1) a fraction of HMW‐DOM (lipid associated) in estuarine and coastal waters is derived from bacteria and phytoplankton; (2) this fraction of HMW‐DOM is formed by various release processes of bacterial membrane components and bacterial reworking of phytoplanktonderived material; (3) this fraction of HMW‐DOM is generally present in all samples from different coastal systems despite variable organic matter inputs and environmental conditions, suggesting an important bacterial role in HMW‐DOM formation.

No evidence for DUP25 in patients with panic disorder using a quantitative real-time PCR approach - Johannes Schumacher; Andreas C. J. Otte; Tim Becker; Yuli Sun; Thomas F. Wienker; Brunhilde Wirth; Petra Franke; Rami Abou Jamra; Peter Propping; Jrgen Deckert; Markus M. Nthen; Sven Cichon (Human Genetics, 2003)

Cloning and characterization of leaf cDNAs that are differentially expressed between wheat hybrids and their parents - L. M. Wu; Z. F. Ni; F. R. Meng; Z. Lin; Q. X. Sun (Molecular Genetics and Genomics, 2003)

EGF Stimulates Growth by Enhancing Capacitative Calcium Entry in Corneal Epithelial Cells - H. Yang; X. Sun; Z. Wang; G. Ning; F. Zhang; J. Kong; L. Lu; P. S. Reinach (The Journal of Membrane Biology, 2003)

Adsorption of Paraquat onto Activated Bleaching Earth - W. T. Tsai; M. F. Hsieh; H. F. Sun; S. F. Chien; H. P. Chen (Bulletin of Environmental Contamination and Toxicology, 2002)

Mapping quantitative trait loci for milling quality, protein content and color characteristics of rice using a recombinant inbred line population derived from an elite rice hybrid - Y. F. Tan; M. Sun; Y. Z. Xing; J. P. Hua; X. L. Sun; Q. F. Zhang; H. Corke (Theoretical and Applied Genetics, 2001)

Effect of Probenecid on Fluorescein Transport in the Central Nervous System Using In Vitro and In Vivo Models - Haiying Sun; Donald W. Miller; William F. Elmquist (Pharmaceutical Research, 2001)

Distribution of allozymic alleles and genetic diversity in the American Barley Core Collection - F. Liu; G.-L. Sun; B. Salomon; R. von Bothmer (Theoretical and Applied Genetics, 2001)

Residuary Toxic Elements And PAHs in Sediments of the Zbiornik Gilow Tailings Pond and Zimmica Stream from Lubin District, Southwest Poland - Yu-Zhuang Sun; A. Leischner; F.-J. Göbbels (Environmental Geochemistry and Health, 2000)

Developmental changes in structure and polypeptide profile of the androgenic gland of the freshwater prawn Macrobrachium rosenbergii - Piera S. Sun; Tina M. Weatherby; Marilyn F. Dunlap; Kristi L. Arakaki; Donis T. Zacarias; Spencer R. Malecha (Aquaculture International, 2000)

The enzymes involved in synthesis and utilization of carbamylphosphate in the deep-sea tube worm Riftia pachyptila - V. Simon; C. Purcarea; K. Sun; J. Joseph; G. Frebourg; J.-P. Lechaire; F. Gaill; G. Hervé (Marine Biology, 2000)

Study on binding of REEs with water-soluble polysaccharides in fern - Y. Q. Wang; J. X. Sun; F. Q. Guo; Z. Y Zhang; H. M. Chen; L. Xu; G. Y. Cao (Biological Trace Element Research, 1999)

Association of genetic polymorphisms of alcohol-metabolizing enzymes with excessive alcohol consumption in Japanese men - F. Sun; I. Tsuritani; R. Honda; Z.-Y. Ma; Y. Yamada (Human Genetics, 1999)

Association of genetic polymorphisms of alcohol-metabolizing enzymes with excessive alcohol consumption in Japanese men - F. Sun; I. Tsuritani; R. Honda; Z.-Y. Ma; Y. Yamada (Human Genetics, 1999)

Low-Cot DNA sequences for fingerprinting analysis of germplasm diversity and relationships in Amaranthus - Mei Sun; H. Chen; F. C. Leung (Theoretical and Applied Genetics, 1999)

Regulation of cell survival in CD95-induced T cell apoptosis: role of NF-κB/Rel transcription factors - A. Lamberti; M. F. Romano; V. Agosti; C. Garbi; S.-C. Sun; H.M. Bond; P. Bonelli; M. C. Turco; S. Venuta (Apoptosis, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Surface-Layer Fluxes in Stable Conditions - J. F. Howell; J. Sun (Boundary-Layer Meteorology, 1999)

The Main Features of the Local Geological Conditions Can Explain the Macroseismic Intensity Caused in Xiji-Langfu (Beijing) by the M s = 7.7 Tangshan 1976 Earthquake - R. Sun; F. Vaccari; F. Marrara; G. F. Panza (Pure and Applied Geophysics, 1998)

Interleukin-13 increases prostaglandin E2 (PGE2) production by normal human polymorphonuclear neutrophils by enhancing cyclooxygenase 2 (COX-2) gene expression - C.-L. Yu; M.-H. Huang; Y.-Y. Kung; C.-Y. Tsai; Y.-Y. Tsai; S.-T. Tsai; D.-F. Huang; K.-H. Sun; S.-H. Han; H.-S. Yu (Inflammation Research, 1998)

Genetic diversity and relationships detected by isozyme and RAPD analysis of crop and wild species of Amaranthus - K. F. Chan; M. Sun (Theoretical and Applied Genetics, 1997)

Assignment of porcine ceruloplasmin and v-RAF1 murine viral oncogene homolog 1 to Chromosome 13 by linkage analysis - H. Sunny Sun; Lizhen Wang; Max F. Rothschild; Christopher K. Tuggle (Mammalian Genome, 1997)

Stimulation of testicular function by exogenous testosterone in male protandrous black porgy, Acanthopagrus schlegeli - E.‐L. Lau; B.‐Y. Lin; F.‐Y. Lee; L.‐T. Sun; S. Dufour; C.‐F. Chang (Journal of Fish Biology, 1997)
When 4 mg of testosterone (T) per kg food was given to 1‐year‐old protandrous male black porgy Acanthopagrus schlegeli for 7 months, gonadosomatic index was significantly higher than when the dose was 0.5 mg kg −1 food. Both doses of T prolonged the spawning season, and increased the number of spermiating fish and milt volume. Sperm concentrations were similar in spermiating black porgy from the treated and control groups. Low levels of oestradiol‐17β were observed during the experimental period while elevated levels of plasma T were observed only in March in both control and T‐treated groups. Significantly higher levels of plasma 11‐ketotestosterone (11‐KT) were observed in the 0.5‐ and 4.0‐mg T‐treated groups during the spawning season as compared to the control group. The present data suggest that both 0.5‐ and 4·0‐mg T doses stimulate testicular weight, increase numbers of spermiating males and milt volume without affecting the sperm concentrations. Plasma 11‐KT concentrations were elevated during T treatment and closely correlated with testicular development and spermiation.

Quantification of bacteriophages ofBacteroides fragilis in environmental water samples of Seine River - Z. P. Sun; Y. Levi; L. Kiene; N. Dumoutier; F. Lucena (Water, Air, & Soil Pollution, 1997)

QUANTIFICATION OF BACTERIOPHAGES OF BACTEROIDES FRAGILIS IN ENVIRONMENTAL WATER SAMPLES OF SEINE RIVER - Z. P. SUN; Y. LEVI; L. KIENE; N. DUMOUTIER; F. LUCENA (Water, Air, & Soil Pollution, 1997)

A medium-density genetic linkage map of the bovine genome - W. Barendse; D. Vaiman; S. J. Kemp; Y. Sugimoto; S. M. Armitage; J. L. Williams; H. S. Sun; A. Eggen; M. Agaba; S. A. Aleyasin; M. Band; M. D. Bishop; et al. (Mammalian Genome, 1997)

Elimination of polychlorinated dibenzofurans (PCDFs) and polychlorinated biphenyls (PCBs) from human blood in the Yusho and Yu-Cheng rice oil poisonings - John J. Ryan; Dan Levesque; Luz G. Panopio; Wing F. Sun; Yoshito Masuda; Hiroaki Kuroki (Archives of Environmental Contamination and Toxicology, 1993)

S-Phenylcysteine formation in hemoglobin as a biological exposure index to benzene - William E. Bechtold; James D. Sun; Linda S. Birnbaum; Songnian N. Yin; Guilan L. Li; Stephen Kasicki; George Lucier; Rogene F. Henderson (Archives of Toxicology, 1992)